Role of glutamine in promoting the proliferation and chondrogenic differentiation of ATDC5 cells: based on transcriptomic analysis - Rui-hao Zhang; Wen-huan Yuan; Ze-long Wang; Qi-rui Yang; Yi Sun; Quan-nian Shao; Wen-ji Wang; Jing Wang (Molecular Biology Reports, 2026)

Lateral impact performance of concrete-encased concrete-filled steel tubular (CECFST) members after exposure to fire: Tests and analysis - Yuan Zheng; Wen-Da Wang; Sun-Hang Ji; Yan-Li Shi; Wei Xian; Rui Wang (Engineering Structures, 2026)

A low-molecular-weight glucan from Lycium barbarum reprograms tumor-associated macrophages involving the Dectin-1/NOX2 axis to suppress hepatoma - Yanping Cai; Yunliang Chen; Chunjing Li; Hongxu Chen; Yi Ji; Shaojie Zhang; Ying Zhu; Shuiling Cao; Rui Xu; Xueqian Xie; Qi Yi; Qing Wang; et al. (Carbohydrate Polymers, 2026)

Biochar strengthens rainfall regime resistance of soil inorganic C by enhancing pH–bicarbonate and carbonic anhydrase regulation in dryland region - Yuhao Wang; Yanbo Ji; Shutong Guo; Lin Sun; Enke Liu; Zhikuan Jia; Kadambot H.M. Siddique; Rui Qian; Ting Wei; Peng Zhang (Agriculture, Ecosystems & Environment, 2026)

Geochronology and Geochemistry of Cretaceous volcanic rocks in the Central Lhasa Block, China: Constraints on the evolution of the Neo-Tethys Ocean - Zhi-Qiang Kang; Rui Wang; Chun-Xi Shan; Ji-Feng Xu; Feng Yang; Sheng-Liang Pei; Ji-Zhong Mu; Ling-Ling Wu; Lu Zhou (Journal of Asian Earth Sciences, 2026)

Prenatal exposure to outdoor artificial light at night and neonatal thyroid function: Identifying critical windows of susceptibility - Wanting Miao; Yanling Shu; Qing Fang; Gaojie Fan; Jing Peng; Li Zhang; Binghai Liu; Wenwen Guo; Lianyan Yan; Jiaoyan Li; Rui Chen; Xiaoning Lei; et al. (Environmental Pollution, 2026)

Rapid inverse design of double-curved beams for multi-stable metamaterials based on prescribed deformation histories through artificial neural network - Chun-Zheng Zhao; Xin Wang; Rui Zhang; Yongfeng Jiang; Haibo Ji; Zhen Li; Bingyang Li; Pengfei Wang; Feng Jin; Tian Jian Lu (Engineering Structures, 2026)

Upcycling hazardous electric arc furnace dust into defect-rich ZnO/ZnFe2O4 heterojunction for in situ H2O2 electrogeneration and water purification - Lijuan Jia; Bo Liu; Guoxing Mu; Yiqiang Ji; Fang Wang; Rui Cao; Ping Ning; Shuo Cui; Jiayu Feng (Chemical Engineering Journal, 2026)

Exploring the mechanism of platycodon grandiflorum saponins in treating Mycoplasma pneumoniae pneumonia based on intestinal microbiota and metabolomics - Rui Shuang Ji; Yun Fei Yang; Chan Yu Wu; Zhen Jing Yang; Jin Zhao Du; Jing Huang Fu; Lin Yao; Wei Ming Wang (Food Bioscience, 2026)

Spatiotemporal dynamics of land degradation in the three gorges reservoir area and its coupling mechanisms with biodiversity and human activity intensity - Cuicui Ji; Hao Cui; Rui Ma; Dandan Ke; Xia Li; Fenglei Han; Xizeng Huang; Jie Liu; Gang Yang; Liejian Wang (CATENA, 2026)

Change of aerosol properties and transport mechanisms in Beijing during 2021-2024 - Rui Xu; Linlu Mei; Kai Ji; Gerrit de Leeuw; Zhibin Lai; Feiyang Wang; Yongliang Yang; Xinhong Zhang; Ruilai Nie (Atmospheric Pollution Research, 2026)

Remote sensing of rural clean heating impacts on air quality: An STL-Q3 framework in Henan Province, China - Yongliang Yang; Wenqiang Guo; Zhitao Zhou; Kai Ji; Zhibin Lai; Rui Xu; Feiyang Wang; Linlu Mei (Remote Sensing Applications: Society and Environment, 2026)

A Hausdorff-guided deep learning approach for tracking the motion of rotating Arctic ice floes - Adan Wu; Tao Che; Chengzhu Ji; Xiaowen Zhu; Rui Zhang; Jinlei Chen; Liuhao Wang; Qingchao Xu; Shengpeng Chen (Ocean Engineering, 2026)

Optimizing pe+pH via integrated water management and phosphorus fertilization enhances phytoextraction of Cd/As by rice plant in contaminated paddy soils - Rui Huang; Yunhe Xie; Xin Wang; Wei Wei; Bingyu Li; Jingmin Yang; Haoyu Chen; Saihua Liu; Xionghui Ji (Journal of Environmental Sciences, 2026)

Optimization of magnetic field-assisted freezing via response surface methodology and its impact on blueberry freeze-thaw quality - Bowen Chen; Xinqun Zhou; Jing Sun; Rui Wang; Min Zhang; Ning Ji; Tingchao Liu; Bangdi Liu; Lihua Jiang (International Journal of Refrigeration, 2026)

Lipid-driven modulation of milk/soy proteins digestion in young child formulas: From in vitro gastric emptying to intestinal absorption coupled with in vivo protease activation - Qiaoya Mo; Jiahui Wang; Chang Xu; Xia Fan; Tao Lin; Kai Ma; Changliang Zhang; Shuo Geng; Feng Ji; Xin Rui; Wei Li (Food Research International, 2026)

Bilayer encapsulation strategy enabled ultra-stretchable electronic skin for human-machine interaction - Miao Kong; Yuxin Chen; Shengwei Gao; Xue Wang; Jiaxin Zhuang; Panqi Huang; Zifan Li; Xu Wang; Zilin Wang; Yuqing Zhang; Ji Cheng; Ruiqi Guo; et al. (Chemical Engineering Journal, 2026)

Short-term organic fertilizer substitution: effects on crop yield and soil phosphorus dynamics in a rice-rapeseed rotation system - Hui Wang; Wenlong Cheng; Shang Han; Shan Tang; Fahui Jiang; Rongyan Bu; Min Li; Rui Zhu; Mengmeng Tang; Zhenghua Xu; Ji Wu (Journal of Soils and Sediments, 2026)

Dihydromyricetin attenuates LPS-induced liver injury in chicks through the JNK signaling pathway - Lina Jia; Jiarui Liu; Zhenghua Ji; Liang Yuan; Yingchao Gong; Xinru Jiang; Xianan Fan; Changwen Li; Rui Li; Haoran Wang; Fangping Liu (Research in Veterinary Science, 2026)

Microplastics enrich and disseminate antibiotic resistance genes in seawater: Enhanced effects of aging and biodegradability of microplastics - Jianhong Shi; Chengyuan Ji; Chaoli Sun; Changhai Jiang; Baoyi Lv; Rui Wang (Journal of Environmental Chemical Engineering, 2026)

Centralized mechanical e-waste dismantling is associated with lower farmland soil heavy metal pollution and carbon emission intensity - Yu Zhang; Ming-jiang He; Wei-jun Fu; Jie Wang; Ke-li Zhao; Xiang-rui Xu; Ji-zi Wu (Journal of Environmental Chemical Engineering, 2026)

Zircon U-Pb dating and geochemistry of the Paleoproterozoic tuffs from the Nsama formation in northeastern Zambia - Jun-ping Ren; A-lei Gu; Hong-wei Sun; Li-bo Zuo; Jie Wang; Bao-jin Zhao; Evaristo Kasumba; Shi Xing; Zi-jiang Liu; Jin-meng Dong; Jin-rui Zhang; Ji-hai Chen (Journal of African Earth Sciences, 2026)

Rfx5 acts as a master regulator of MHC class I and class II gene expression in zebrafish immunity - Rui Liu; Xiangmin Zhang; Xiu Yin; Ailong Zhang; Yunchao Wang; Lu Wang; Guangdong Ji; Hongyan Li (Fish & Shellfish Immunology, 2026)

A comprehensive review on the main alkamides in Piper nigrum and anti-inflammatory properties of piperine - Rui Guo; Yiming Fang; Junyao Li; Haoyang Gao; Zhiqiang Niu; Yadong Lv; Long You; Ji Zhang; Xu Wang; Guiping Wu; Taoyun Wang; Weicheng Hu; et al. (Phytochemistry Reviews, 2026)

Ultra-low temperature adsorption of propane to achieve layered Ni3V2O8/NiO synergistic catalysed oxidative dehydrogenation of propane to propylene - Rui Liao; Yun Yang; Peiting Jiang; Fengyu Ji; Yuhang Qian; Lulu Li; Xuyu Wang; Xinwei Zhou; Hongbing Ji (Fuel, 2026)

The light side of the microbiome in trauma: Mechanism and applications - Han-Yue Luo; Lei-Ming Cao; Kan Zhou; Yi-Fu Yu; Yao Xiao; Guang-Rui Wang; Bing Liu; Qiu-Ji Wu; Xiao-Long Wang; Zhi-Yong Song; Lin-Lin Bu (Chemical Engineering Journal, 2026)

Nitrogen and phosphorus limitation patterns of microbial nitrogen cycling traits in an arid soil - Hongfei Ji; Ying Wang; Rui Wang; Shengli Guo (Journal of Soils and Sediments, 2026)

Metabolomic changes following PMSG-induced estrus synchronization in Qianbei Ma goats - Feng-Xin Qiao; Yong-Hong Ju; Xiao-Dong Wang; Peng-Cheng An; Quan Ji; Rui-Yang Li; Ting-Ji Zeng; Qing Liu; Dai-Yue Zhang; Zu-Han Feng; Mao-Sheng Cao; Xiang Chen (Animal Reproduction Science, 2026)

Geochemistry of tourmaline in granitic rocks from the Zharigana and Caolong areas, Northern Tibet: Implications for the identification of lithium-mineralizing plutons - Ling Ma; Jin-Sheng Zhou; Qiang Wang; Lin Ma; Jin-Heng Liu; Wu-Fu Li; Bing-Zhang Wang; Chun-Tao Wang; Jian-Dong Liu; Xin-Yuan Zhang; Mao-Rui Liu; Zhi-Wei Yu; et al. (Lithos, 2026)

Life-cycle carbon footprints of rural toilet systems in China: Hotspot diagnosis and mitigation pathways - Rui Ma; Xiangwen Jia; Yilan Cheng; Sen Cen; Qian Wang; Zeye Zou; Fangying Ji; Xiaoming Wang (Journal of Cleaner Production, 2026)

Effective recovery of Dy from LiCl-KCl molten salt via controlled potential on Ga electrode: Mechanism, kinetics and thermodynamics of electrode reaction - Yuying Xiao; Wenlong Li; Rui Li; Ziqin Huang; Ming Gong; Jiandong Li; Ji Wang; Lifeng Chen; Shunyan Ning; Xiangbiao Yin; Wei Han; Yuezhou Wei (Journal of Environmental Chemical Engineering, 2026)

Efficient regeneration of deactivated VPO catalysts: Reconstructing the catalyst active structure via a mild reduction-reoxidation-reaction stabilization process - Jiale Xu; Fei Wang; Renjie Ji; Xiaoyu Yan; Rui Huang; Chunyi Li (Chemical Engineering Journal, 2026)

Ferrate-assisted nonthermal plasma for efficient PFOA degradation in landfill leachate: Mitigating bulk organic interference and enhancing application potential - Changtao Chen; Zhuofan Yu; Rui Zhang; Xuetong Yang; Qintong Wang; Yuxian Ji; Xiaoyu Cheng; Jun Li; Anton Nikiforov; Stijn W.H. Van Hulle; Bo Lai (Water Research, 2026)

Macro-micro scales insights into the effect of enrofloxacin on the Fe-C-Anammox system: Performance enhancement, metabolic optimization, and ARGs reduction - Rui Zhong; Jiaqi Lu; Liping Xie; Xiao-Ming Ji; Qi Zhang; Xiao Ma; Wenru Liu; Ying Wang (Journal of Water Process Engineering, 2026)

Alpaca nanobody-based sandwich ELISA for specific detection of Salmonella enteritidis in chicken - Liang Yuan; Shibo Wang; Yani Ren; Zhenghua Ji; Xinru Jiang; Beili Hao; Shuangshuang Hao; Xiaoxi Han; Changwen Li; Yicong Chang; Rui Li; Fangping Liu (Food Control, 2026)

Ecosystem-specific composition and drivers of plastisphere resistome in freshwater and marine environments - Jianhong Shi; Chaoli Sun; Yinglong Su; Yifan Wu; Min Zhan; Chengyuan Ji; Rui Wang; Baoyi Lv (Environmental Research, 2026)

Deriving predicted no-effect concentrations for PFASs to protect threatened and endangered fish: A comparison of water- andtissue-residue-based toxicity data - Jiayu Wang; Xiaolei Wang; Qingyuan Cao; Rui Wang; Yuanpu Ji; Jing Zhang; Fengchang Wu; Zugen Liu; Xiaoli Zhao (Environmental Research, 2026)

Cytoplasmic-nuclear remote suppression of c-MYC induces cell cycle arrest and enhances radiotherapy sensitivity in liver cancer via biohybrid platelets - Lin Xiao; Fei Ge; Qinyu Ji; Rui Ji; Yan Wang; Shaoqing Ju; Ming Cui; Donglin Xia; Rongrong Jing (Chemical Engineering Journal, 2026)

Correction to: Genetic Mapping of the Wheat Dimeric α-Amylase Inhibitor Multi-Gene Family Using Allele-Specific Primers Based on Intergenomic SNPs - Ji-Rui Wang; Yu-Ming Wei; Ze-Hong Yan; You-Liang Zheng (Plant Molecular Biology Reporter, 2026)

Soil biogeochemical controls on the distribution of phosphorus fractions in the Qilian Mountains of China’s drylands - Zeng-Ru Wang; Ji-Liang Liu; Feng-Rui Li (Plant and Soil, 2026)

Ginkgonins A and B: Two new sesquiterpenoids from Streptomyces ginkgonis TH01 - Yun-Fei He; Jing Miao; Chao Jian; Rui-Jun Wang; Yong-Sheng Gao; Jie-Hao Jin; Xiao-Yi Chen; Ji-Dong Wang; Shao-Yong Zhang (Phytochemistry Letters, 2026)

New insights into the interaction between bacterioplankton community and dissolved organic matter driven by river connectivity - Jianghao Ji; Xiong Cao; Rui Wang; Jianguo Tao; Mochen Wu; Yuanze Sun; Jiangyong Chu; Xin Kou; Xiaofeng Cao; Jie Wang; Jianfeng Peng (Journal of Environmental Management, 2026)

Alkali-induced molecular aggregation enabled rapid-forming PVA hydrogel electronic skin with multifunctional integration of protection, EMI shielding, and sensing - Di Liu; Yang Lyu; Zhongying Ji; Rui Guo; Zhihan Hong; Xiaolong Wang; Xinyan Shi (Chemical Engineering Journal, 2026)

Patterns of phoD- and pqqC-containing bacterial communities and their potential linkages with soil P cycle multifunctionality under long-term crop rotations - Hongfei Ji; Yan Chen; Ying Wang; Rui Wang; Shengli Guo (Plant and Soil, 2026)

Spatiotemporal modeling of oxygen transport and layered regulation in tidal flow constructed wetlands - Rui Ma; Lanlan Fu; Jiangsen Ma; Lei Jiang; Yiyuan Zhuo; Linsong Cheng; Fangying Ji; Xiaoming Wang (Water Research, 2026)

Brominated organic compounds in leachate across China: Occurrence and molecular variations - Jing Zheng; Ji-Tao Lv; Yue Sun; Qing-Yu Liu; Qiu-Rui Zhang; Zi-Meng Wang; Xiao-Song He (Water Research, 2026)

Rice SINA E3 ligases dichotomously control ERECTA1 ubiquitination and stability to regulate panicle morphogenesis and grain yield - Zi-Qi Lu; Tao Guo; Ying-Jie Cao; Jun-Xiang Shan; Wang-Wei Ye; Nai-Qian Dong; Yi Kan; Yi-Bing Yang; Shuang-Qin Guo; Jie-Jie Lei; Xiao-Rui Mu; Ji-Fu Zhou; et al. (Molecular Plant, 2026)

Genome-wide analysis of the sugarcane SUT gene family reveals ShSUT4 as a key regulator of abiotic stress responses - Xue-Ting Zhao; Ahmad Ali; Cui-Lian Feng; Ji-Shan Lin; Rui-Jie Wu; Shu-Zhen Zhang; Guang-Run Yu; Hai-Feng Jia; Yu-Qing Gong; Ting-Ting Zhao; Jun-Gang Wang (Theoretical and Applied Genetics, 2026)

Spatial aggregation trends of cultivated land quality and landscape patterns: A remote sensing analysis - Mengmeng Tang; Wenlong Cheng; Zhengbao Gao; Fahui Jiang; Shang Han; Danyang Xu; Rongyan Bu; Shan Tang; Rui Zhu; Min Li; Hui Wang; Changai Lu; et al. (Applied Soil Ecology, 2026)

A registration and construction quality analysis framework for low quality hull block point cloud with extensive redundant structures - Shilin Huo; Ji Wang; Rui Li; Yujun Liu; Lin Pang; Jian Zhang (Ocean Engineering, 2025)

Numerical calculation of line heating for hull curved plate based on strain direct boundary - Shun Wang; Haohao Jia; Yuxuan Fu; Ji Wang; Rui Li (Ocean Engineering, 2025)

A high strength, breathable, water resistant chitosan-gelatin composite film modified by tannic acid-synergistic ZIF-8 for blueberry preservation - Huixuan Zhang; Xue Yang; Yingying Zhang; E. Zhao; Haimiao Tian; Keshan Wang; Ning Ji; Yuanyuan Liu; Rui Wang (Food Packaging and Shelf Life, 2025)

Synergistic confinement and heavy atom effects in carbon dots for enhanced phosphorescence: Matrix-free and matrix conditions - Rui Li; Linping Zhang; Ji Fan; Bijia Wang; Hong Xu; Zhiping Mao (Chemical Engineering Journal, 2025)

3D printed hydrogel with fingerprint-inspired features for enhanced sensing performance in electronic skin - Jianshe Hao; Yanbin Xu; Chaofan Yang; Rui Guo; Yang Lyu; Zhongying Ji; Xiaolong Wang (Chemical Engineering Journal, 2025)

A new isopropanol-intermediate mechanism for CO2-assisted propane dehydrogenation over ZIF-derived (GaCe)Ox: Toward propylene synthesis - Yun Yang; Rui Liao; Rulan Pu; Peiting Jiang; Lulu Li; Xuyu Wang; Hongbing Ji (Chemical Engineering Journal, 2025)

Cryogenic pre-activation induces structural optimization and performance boost for Li-rich Mn-based cathodes - Rui-Chi Li; Lan-Fang Que; Jun-Sen Jiang; Fu-Da Yu; Ji-Huai Wu; Xuan Wang; Can-Zhong Lu; Yi-Ming Xie (Chemical Engineering Journal, 2025)

Structural and physicochemical characterization of plant-derived galactomannans: revealing promising substrates for mannooligosaccharides production - Shujun Hou; Yijin Zhang; Rui Yang; Wei Xu; Huanli Wang; Zhijin Zhang; Botao Liu; Guiyao Dai; Ting Wang; Pengfei Li; Liang He; Ke Wu; et al. (Carbohydrate Polymers, 2025)

Protection against intestinal damage in female Drosophila melanogaster: Comparative contribution of arabinoxylan and its non-covalent/covalent complexes with catechin - Dima Atehli; Tianyu Qi; Rui Liu; Wan Wang; Qiaomei Zhu; Yuanlin Sun; Qingbin Guo; Ji Kang (Bioactive Carbohydrates and Dietary Fibre, 2025)

CLDN4 promotes ferroptosis and inflammation involving JAK2/STAT3 pathway in acute pancreatitis - Chuanming Zheng; Rui Tao; Zhenjie Wang; Xi Zhang; Hai Jiang; Zhong Ji; Hehe Dou; Zhaohui Du (Functional & Integrative Genomics, 2025)

Application of ambient noise tomography to coastal granite islands: A case study of Wuzhizhou Island in Hainan, China - Cheng Huang; Sheng Liu; Jun-Qiao Long; Chang-Rong Zhang; Bo Xiao; Da-Cheng Wang; Cheng-Long Wei; Rui Wang; Li Yan; Xuan Hu; Zhuo Xin; Xiu-Ji Meng; et al. (Applied Geophysics, 2025)

Injectable Hyaluronic Acid Hydrogels Crosslinked by Structure-engineered Aldehyde-functionalized β-Cyclodextrin Derivatives for Long-term Controlled Voriconazole Delivery - Chao Yang; Meng Xin; Yufu Jiang; Wenqian Wang; Wenhui Li; Junlin Quan; Wancong Zhou; Rui Yuan; Zhe Chen; Depeng Shi; Zhijian Ji; Xingxing Yue; et al. (AAPS PharmSciTech, 2025)

Hydrodynamic force analysis of semi-submerged propeller and influence on shaft whirling vibrations - Fangshuai Wei; YuJun Liu; Ji Wang; Rui Li; Lin Pang (Ocean Engineering, 2025)

Elucidation of the molecular mechanism for the phenolic acid removing the fishy odor bound to proteins in sea bass - Huanqing Lei; Yaoxing Chen; Rui Wang; Qiaohui Zeng; Langhong Wang; Jian Li; Wenhao Lin; Xinan Zeng; Zhong Han; Ji Ma; Ruoyong Wang (Food Chemistry, 2025)

Revealing the differences and similarities in the in-situ and ex-situ activation of VPO catalysts to further optimize the activation process - Jiale Xu; Renjie Ji; Xiaoyu Yan; Rui Huang; Fei Wang; Jianxiang Li; Chunyi Li (Chemical Engineering Journal, 2025)

Marine Hydrogen Pressure Reducing Valves: A Review on Multi-Physics Coupling, Flow Dynamics, and Structural Optimization for Ship-Borne Storage Systems - Heng Xu; Hui-Na Yang; Rui Wang; Yi-Ming Dai; Zi-Lin Su; Ji-Chao Li; Ji-Qiang Li (Journal of Marine Science and Engineering, 2025)
As a zero-carbon energy carrier, hydrogen is playing an increasingly vital role in the decarbonization of maritime transportation. The hydrogen pressure reducing valve (PRV) is a core component of ship-borne hydrogen storage systems, directly influencing the safety, efficiency, and reliability of hydrogen-powered vessels. However, the marine environment—characterized by persistent vibrations, salt spray corrosion, and temperature fluctuations—poses significant challenges to PRV performance, including material degradation, flow instability, and reduced operational lifespan. This review comprehensively summarizes and analyzes recent advances in the study of high-pressure hydrogen PRVs for marine applications, with a focus on transient flow dynamics, turbulence and compressible flow characteristics, multi-stage throttling strategies, and valve core geometric optimization. Through a systematic review of theoretical modeling, numerical simulations, and experimental studies, we identify key bottlenecks such as multi-physics coupling effects under extreme conditions and the lack of marine-adapted validation frameworks. Finally, we conducted a preliminary discussion on future research directions, covering aspects such as the construction of coupled multi-physics field models, the development of marine environment simulation experimental platforms, the research on new materials resistant to vibration and corrosion, and the establishment of a standardized testing system. This review aims to provide fundamental references and technical development ideas for the research and development of high-performance marine hydrogen pressure reducing valves, with the expectation of facilitating the safe and efficient application and promotion of hydrogen-powered shipping technology worldwide.

“Phenology description is all you need!” mapping unknown crop types with remote sensing time-series and LLM generated text alignment - Siyuan Wen; Wenzhi Zhao; Fengcheng Ji; Rui Peng; Liqiang Zhang; Qiao Wang (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Sunlight-activated photochromic-photothermal nanofibrous textiles for self-monitored thermal management - Shuai Liang; An-Yang Duan; Shi-Kun Yan; Yan-Rui Zhao; Jin Zhang; Guo-Wei Xiao; Chang-Hai Xu; Ji-Xiang Hu; Guo-Ming Wang (Chemical Engineering Journal, 2025)

Halogen-sulfur synergy in benzodithiophene-benzodithienedione conjugated polymers: Molecular design of high-performance photoelectrodes for metal anti-corrosion - Rui Ding; Jin-ying Li; Yi-wen Zhang; Hao-han Cao; Xiao Liu; Yu-han Wang; Ming-di Lei; Yu-lin Zhang; An-lan Ji; Yu-chen Zhang; Jie Liu; Tai-jiang Gui; et al. (Chemical Engineering Journal, 2025)

Bioactivity of essential oils extracted from four varieties of Zanthoxylum bungeanum against insects and dominant spoilage fungi in Codonopsis pilosulae - Rui Feng; Zhenjia Ma; Jiali Bai; Jie Fan; Chunyu HE; Junlong Wang; Ji Zhang; Junyu Liang; Feng Zhou (South African Journal of Botany, 2025)

Mechanistic insights into the impact of Lincomycin on microalgal-bacterial granular sludge in domestic wastewater treatment - Guihua Wang; Shujuan Meng; Bin Ji; Rui Wang; Min Liao; Xinyu Chang; Yu Liu; Meng Zhang (Journal of Water Process Engineering, 2025)

Moderate ozone application preserves postharvest quality of ‘manaohong’ cherries by enhancing antioxidant defense and membrane stability - Wei Zou; Ning Ji; Yuxin Li; Huali Nie; Qi Gao; Rui Wang; Cunkun Chen; Bangdi Liu (Journal of Stored Products Research, 2025)

Sub-soil biodegradable film mulching: A sustainable solution for enhancing winter wheat yield and shaping soil microbial communities in saline-alkali soils - Changyuan Wang; Junwei Dong; Boxiang Ji; Yahui Lv; Yixuan Song; Quanqi Li; Chitao Sun; Rui Zong; Mingming Zhang (Journal of Hazardous Materials, 2025)

Catalytic dehydrogenation of propane by electrospinning one-dimensional Zn-Ga2O3-Al2O3 nanofibres under CO2 atmosphere - Rui Chen; Xue Han; Yixuan Yang; Xupeng Yang; Yuqi Wang; Yupeng Zhang; Tiange Huang; Jie Wei; Junjie Ding; Xuyu Wang; Hongbing Ji (Fuel, 2025)

Electrochemical CO2 reduction via strain-engineered AuPd alloy catalysts - Shangdong Ji; Qian Wang; Jiapeng Huang; Ruiyun Guo; Yanan Li; Yangzi Zheng; Rui Li; Yaohui Zhao; Chao Wu; Mingshang Jin (Chemical Engineering Journal, 2025)

Doping potassium to modulate the surface properties of CuO/SiO2 for selective oxidation of isobutane to tert-butanol - Renjie Ji; Jiale Xu; Rui Huang; Xiaoyu Yan; Fei Wang; Chunyi Li (Chemical Engineering Journal, 2025)

Enhancing Mnammox-driven nutrient removal in manganese ore-based constructed wetlands: The electron-shuttling role of straw-released humus - Rui Ma; Yiyuan Zhuo; Jintao Lei; Lanlan Fu; Jiangsen Ma; Linsong Cheng; Fangying Ji; Xiaoming Wang (Chemical Engineering Journal, 2025)

PED-TRFIA: PEDV early on-site detection based on the time-resolved fluorescence ImmunoAssay - Bin Wang; Hongli Li; Rui Liang; Tingting Fu; Shusen Ji; Boya Li; Peichen Zhang; Haiyang Wu; Wenting Wang; Lianmei Bai; Xiuju Yu; Wei Hou; et al. (Analytica Chimica Acta, 2025)

Depletion of Albendazole and Its Metabolites and Their Impact on the Gut Microbial Community Following Multiple Oral Dosing in Yellow River Carp (Cyprinus carpio haematopterus) - Yue Liu; Yan Dai; Yan-Ni Zhang; Wen-Rui Wang; Yu-Xin Chen; Yang-Guang Jin; Long-Ji Sun; Shi-Hao Li; Fang Yang; Xing-Ping Li; Fan Yang (Fishes, 2025)
Healthy Yellow River carp (Cyprinus carpio haematopterus) reared at a water temperature of 23 ± 0.6 °C were orally administered albendazole (ABZ) at a dose of 12 mg/kg body weight (BW) once daily for seven consecutive days. At predetermined time points after the final administration, five fish were randomly selected for sampling. Plasma, skin-on-muscle, liver, and kidney tissues were collected, and the concentrations of ABZ and its three metabolites—albendazole sulfoxide (ABZSO), albendazole sulfone (ABZSO2), and albendazole-2-aminosulfone (ABZ-2-NH2−SO2)—were determined using high-performance liquid chromatography (HPLC). The results indicated that ABZ and ABZSO were widely distributed across tissues, while ABZSO2 and ABZ-2-NH2-SO2 were only present at trace levels. Pharmacokinetic analysis of ABZ and ABZSO in plasma and tissues was performed using noncompartmental analysis (NCA). ABZ peaked in plasma at 0.73 μg/mL at 24 h after the last administration, with an elimination half-life (t1/2λZ) of 38.56 h. ABZSO reached a peak plasma concentration of 1.54 μg/mL at 24 h, with a t1/2λZ of 53.73 h. According to China’s national standard, where ABZ-2-NH2−SO2 is the marker residue with a maximum residue limit (MRL) of 100 μg/kg in fish skin-on muscle, no withdrawal period was necessary. However, based on the European Union standard—which uses the sum of ABZ and its three metabolites as the marker residue and an MRL of 100 μg/kg in ruminants—a withdrawal period of 16 days (or 351 °C-days) was required. Additionally, the study assessed changes in the intestinal microbiota following multiple oral doses of ABZ. The results indicated that ABZ administration significantly altered microbial diversity and composition in a dose- and time-dependent manner. After drug withdrawal, the intestinal microbiota gradually returned to baseline levels, similar to the untreated control group.

Resilience-based restoration sequence optimization of disrupted transportation networks: A novel matheuristic approach - Xinhao Cui; Bo Li; Siyue Zhang; Ziguang Ji; Shitao Wang; Rui Luo; Yi Ren; Yiyong Xiao (Transportation Research Part D: Transport and Environment, 2025)

Mitigation of arsenic uptake and accumulation in rice grains by applying husk-derived silicon in a synergistic way: Evidence from pot and field trials - Xianghong LI; Xin WANG; Xionghui JI; Jingmin YANG; Yunping YU; Rui HUANG; Bo PENG; Baoshan XING (Pedosphere, 2025)

Insights into ROL-driven and ROS-mediated metalloid oxidation and sequestration in the soil-rice iron barrier system - Jing-Min Yang; Xin Wang; Dong-Xing Guan; Rui Huang; Xiong-Hui Ji; Yun-He Xie; Bo Peng; Qin-Bo Qin (Journal of Hazardous Materials, 2025)

Adaptive neofunctionalization of ancestral CYP6SN2vB following duplication contributes to abamectin resistance in Chilo suppressalis Walker - Shuai Wang; Yuan Xie; Chong Liu; Jin-Wei Liu; Fang-Rui Guo; Song-Tao Qiao; Yu-Ji Xing; Shun-Fan Wu; Chris Bass; Cong-Fen Gao (Insect Biochemistry and Molecular Biology, 2025)

Laodelphax striatellus salivary sheath protein Lsactin triggers defense response in plants - Liangxuan Qi; Jing Li; Han Wang; Jing Li; Xinyang Tan; Zhichang Zhao; Sicong Zhou; Jichao Fang; Rui Ji (Insect Biochemistry and Molecular Biology, 2025)

Functional nucleic acid-stabilized selenium nanotechnology enable synergistic healing of diabetic chronic wounds - Si-Wei Yang; Jing Wang; Yan Tan; Xiao Jing; Chen-Yu Wang; Zhi-Li Yao; Wen-Hui Wang; Yong-Ji Li; Hao-Rui Li; Yan Zhao; De-Ming Kong; Qi-Liang Cai (Chemical Engineering Journal, 2025)

The combined application of cis-cyclo(L-Phe-L-Pro) with antimicrobial proline-based 2,5-diketopiperazines significantly enhances anti-breast cancer activity by selectively targeting cancer stem cells - Rui Liu; Bo Sun; Sa-Ouk Kang; Yeonju Hong; Ji-Yoon Yeo; Jun-Hua Wang; Min-Kyu Kwak (Chemico-Biological Interactions, 2025)

Response of carbon flux of alpine ecosystems to hydrological and meteorological factors on the Qinghai-Tibet Plateau - Xiuying Wang; Yuancang Ma; Bingrong Zhou; Fu Li; Shulan Su; Huali Du; Honglu Ma; Shujiao Sun; Haijuan Ji; Rui Zhang (Journal of Mountain Science, 2025)

Flash elimination of nano-/microplastics from complex matrices with record efficiency and sustainability - Nuan Liu; Yingxin Ji; Feng Tang; Jianxin Fu; Chuntian Qiu; Rui Wang; Zhiyang Zhang; Lingxin Chen; Guoqing Wang (Chemical Engineering Journal, 2025)

A Computational Study on the Excitation Forces of Partially Submerged Propellers for High-Speed Boats - Fangshuai Wei; Yujun Liu; Ji Wang; Rui Li; Lin Pang (Journal of Marine Science and Engineering, 2025)
During high-speed navigation, boat propellers often become partially exposed due to elevated sailing speeds. This condition results in a unique operational scenario where propellers are only partially submerged. Conducting computational studies on the excitation of propellers under such circumstances is essential for optimizing the dynamic performance of the shafting system. A theoretical calculation method for propeller performance was developed based on the principles of fluid dynamics relevant to water entry, leading to a computational method for determining excitation forces in this specific operational condition. This method was subsequently refined through appropriate adjustments using ANSYS Fluent software to simulate the behavior of partially submerged propellers. The findings highlighted the accuracy of the proposed model in predicting the pulsation of six force components across three distinct directions: along the propeller shaft, vertical, and lateral. Specifically, for a single blade (Blade 1), the pulsation amplitude of the vertical force (Fx) constituted 82.1% of its maximum peak magnitude and equated to 57.5% of the blade’s mean thrust. Analogously, the lateral force (Fz) pulsation amplitude represented 53.3% of its maximum peak magnitude and 40.0% of the mean thrust. These findings indicate the presence of significant unsteady hydrodynamic loads. Furthermore, a visualization approach was presented to analyze blade load phasing, offering insights relevant to the arrangement of blades on partially submerged propellers.

Corrigendum to “Evaluation of the main economic characteristics of a narrow-thallus strain of Neoporphyra haitanensis” [Aquaculture Volume 558: 738395, 15 September 2022] - Rui Zhao; Yan Xu; Kai Xu; Dehua Ji; Changsheng Chen; Wenlei Wang; Chaotian Xie (Aquaculture, 2025)

Comparative mechanisms of PDS-activated antibiotic remediation in groundwater via controlled-release materials with different mesoporous catalysts - Ting Wang; Jing-le Chen; Rui Huang; Hua-li Chen; Cheng Hu; Gang Chen; Kou-ping Chen; Ji-chun Wu (Journal of Environmental Management, 2025)

Au-modified Cu2O with CO-enriched active sites for tandem catalysis of CO2 deep-reduction to C2H4 - Ji-song Yan; Wei Qiu; Hao Liu; Qing-shan Wang; Ling-qi Yu; Sheng-hui Guo; Rui-tang Guo (Journal of Environmental Chemical Engineering, 2025)

Research on the Forming Detection Technology of Shell Plates Based on Laser Scanning - Ji Wang; Baichen Wang; Yujun Liu; Rui Li; Shilin Huo; Jiawei Shi; Lin Pang (Journal of Marine Science and Engineering, 2025)
In order to solve the problems of low efficiency and insufficient accuracy of the traditional manual template method in the forming detection of shell plates, a digital solution based on laser scanning detection system was proposed. By introducing a six-degree-of-freedom robotic arm and a high-precision line laser sensor to build a three-dimensional detection platform, a digital template method framework including data acquisition, point cloud registration, surface reconstruction, and deviation analysis was innovatively constructed. A point cloud non-penetration registration algorithm fused with boundary geometric information was proposed. Based on the improved Delaunay triangulation algorithm, the surface is reconstructed and the digital template is extracted. Experimental verification shows that the method achieves an accuracy of less than 1 mm of error in the detection of outer plates, shortens the single detection time to less than 10 min, and improves the detection efficiency by more than 75% compared with the traditional method.

Tracking of single virus: Dual fluorescent labeling of pseudorabies virus for observing entry and replication in the N2a cells - Mingzhi Li; Li Pan; Caoyuan Ma; Hongxia Wu; Guangtao Xiang; Lian-Feng Li; Tao Wang; Rui Luo; Yongfeng Li; Di Liu; Huanjie Zhai; Moon Assad; et al. (Veterinary Microbiology, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

CORBES: Radiation belt survey with international small satellite constellation - Ji Wu; Li Deng; Jaan Praks; Marius Anger; Philipp Oleynik; Wojciech Hajdas; Jin-Dong Wang; Shen-Yi Zhang; Bin Zhou; Li Zeng; Jinbin Cao; David Fischer; et al. (Advances in Space Research, 2025)

Two new phenolic glycosides from Cyathula officinalis and their relaxant effects on uterine smooth muscle - Mei-Ji Sun; Rui Zhao; Min Wen; Chun-Wang Meng; Hai-Guo Su; Fu-Xin Mi; Cheng Peng; Juan Liu; Liang Xiong (Phytochemistry Letters, 2025)

Corrigendum to ‘Transcriptomic and metabolomic analyses insight into the synergistic effects of nitric oxide and hydrogen sulfide fumigation on enhancing postharvest antioxidant defense and phenylpropane metabolism in ‘crystal’ grape’ [Food Bioscience, Volume 66, April 2025, 106110] - Renchan Liu; Ning Ji; Rui Wang; Yuxin Li; Huali Nie; Cunkun Chen; Bangdi Liu (Food Bioscience, 2025)

Transcriptomic and metabolomic analyses insight into the synergistic effects of nitric oxide and hydrogen sulfide fumigation on enhancing postharvest antioxidant defense and phenylpropane metabolism in ‘crystal’ grape - Renchan Liu; Ning Ji; Rui Wang; Yuxin Li; Huali Nie; Cunkun Chen; Bangdi Liu (Food Bioscience, 2025)

Ionic covalent organic framework engineered super-charged thin-film composite polyamide membrane for desalination - Hui Wang; Rui Ding; Tao Wu; Xianjuan Zhang; Lijuan Cheng; Kai Xu; Yu Zheng; Xiao Pang; Genliang Ji; Liqiang Shen; Junjun Li; Runnan Zhang; et al. (Chemical Engineering Journal, 2025)

Pharmacological Inhibition of TXNRD1 by a Small Molecule Flavonoid Butein Overcomes Cisplatin Resistance in Lung Cancer Cells - Rui Yang; Shibo Sun; Qiuyu Zhang; Haowen Liu; Ling Wang; Yao Meng; Na Chen; Zihan Wang; Haiyan Liu; Fengyun Ji; Yan Dai; Gaohong He; et al. (Biological Trace Element Research, 2025)

Stratigraphy and sedimentology of the upper Pennsylvanian Amushan formation of North China: Palaeogeographic implications for the Eastern Palaeo-Asian Ocean and late palaeozic ice age - Zhongzhao Ding; Shuang Dai; Lingfeng Qin; Chunling Xue; Qiwei Wang; Xin Fan; Xiaojun Ma; Yifeng Hong; Xinnan Fang; Jie Yang; Zhaobin Zhang; Tianqi Ji; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

A small RNA effector conserved in herbivore insects suppresses host plant defense by cross-kingdom gene silencing - Wen-Hao Han; Shun-Xia Ji; Feng-Bin Zhang; Hong-Da Song; Jun-Xia Wang; Xiao-Ping Fan; Rui Xie; Shu-Sheng Liu; Xiao-Wei Wang (Molecular Plant, 2025)

Immune regulation differences in Large yellow croaker with varied resistance to Cryptocaryon irritans infection - Zhou Jiang; Ji Zhao; Rui Li; Qiaozhen Ke; Jiaying Wang; Yin Li; Shuimu Hu; Junjia Zeng; Fei Pu; Ning Li; Peng Xu; Tao Zhou (Fish & Shellfish Immunology, 2025)

Highly stretchable, conductive, and self-adhesive starch-based hydrogel for high-performance flexible electronic devices - Rui Chen; Lei Wang; Dan Ji; Mengqing Luo; Zihao Zhang; Guiyan Zhao; Xiaohua Chang; Yutian Zhu (Carbohydrate Polymers, 2025)

Fertilization effects on soil organic matter chemistry - Dengjie Zhou; Rui Mou; Lihua Wang; Jingru Liu; Yuanxiang Tang; Ji Chen; Petr Heděnec; Zhenfeng Xu; Bo Tan; Xinglei Cui; Han Li; Li Zhang; et al. (Soil and Tillage Research, 2025)

Human cardiac organoid model reveals antibacterial triclocarban promotes myocardial hypertrophy by interfering with endothelial cell metabolism - Nana Yang; Jiahong Chen; Yujie Zhu; Wenxin Shan; Zheng Cao; Yiwen Fu; Huanhuan Cao; Yanyan Li; Yukun Xiang; Shusi Ding; Huiqing Wang; Yaobo Zhao; et al. (Science Bulletin, 2025)

Trimeric tetrapeptide repeat protein TPR16 positively regulates salt stress in apple - Qing Wang; Da-Ru Wang; Xin Liu; Guo-Lin Chen; He-Dan Li; Wen-Long Ji; Man-Shu Qu; Rui Yang; Chun-Xiang You (Journal of Plant Physiology, 2025)

Enhanced electron transport through hydrogen bonds and Ag nanoparticles in the PCN-222/Ag/COF core–shell photocatalyst for efficient oxytetracycline degradation - Bing-Bing Lu; Jia-Chang Lu; Qing-Yun Zhao; Rui Wang; Ze-Lin Chen; Ji-Qiang Guan; Hao Liu; Ying Fu; Fei Ye (Journal of Cleaner Production, 2025)

Relative contributions of climate and grazing to forage supply in the Yellow River source area - Suizi Wang; Jiangwen Fan; Miaomiao Wang; Rui Tang; Nan-Ji Jiang (Journal of Environmental Management, 2025)

Piezoelectric polarization-induced photogenerated carriers transfer coupled with active electron transport Z-scheme heterojunction synergistic optimization of BiFeO3/CdS composite photocatalysts for hydrogen production - Xinyu Ma; Rui Li; Zhao Li; Long Zhang; Yongjie Cao; Kui Nie; Die Zhou; Qing Ji; Cheng Wang; Zehua Zhang; Yutian Li; Meidan Que; et al. (Journal of Environmental Chemical Engineering, 2025)

The characteristics of phthalate acid esters and bisphenol A in PM2.5 of a petrochemical city: Concentrations, compositions, and health risk assessment in Dongying - Fangyun Long; Yanqin Ren; Yuanyuan Ji; Xurong Bai; Hong Li; Gehui Wang; Xiaoyu Yan; Yubao Chen; Junling Li; Haijie Zhang; Rui Gao; Fang Bi; et al. (Environmental Pollution, 2025)

Strengthening H2 gas–liquid mass transfer using superaerophobic cathodes for enhanced methane production from CO2 in H2-mediated microbial electrosynthesis system - Jia-Yao Gao; Wen-Fang Cai; Ji-Rui Bai; Yu-Cheng Zhu; Yu-Xiao Zhang; Sheng Wang; Kun Guo; Qing-Yun Chen; Yun-Hai Wang (Bioresource Technology, 2025)

RNA-Seq-based WGCNA reveals the physiological and molecular responses of poplar leaves to NaHCO3 stress - Song Jiaqi; Wang Jiechen; Qin Rui; Ji Guangxin; Cui Congcong; Sun Nan; Qi Siyue; Ding Changjun; Zhang Huihui (Trees, 2025)

Thirty-year dryland crop rotation improves soil multifunctionality and shifts soil fungal community - Ying Wang; Hongfei Ji; Yan Chen; Rui Wang; Shengli Guo (Plant and Soil, 2025)

Factors governing bark tufa deposition in fluvial systems: the case study of Nuorilang in Jiuzhaigou, Sichuan China - JunHao Li; FuDong Wang; WuYang He; QinYingZi Cai; Shi Chen; GuoQing Huang; Dawood Muhammad; Carlos Pérez-Mejías; Rui Zhang; ZiTong Peng; SiRui Chen; ChenWei Ji; et al. (Carbonates and Evaporites, 2025)

Association Between Exposure to Multiple Toxic Metals in Follicular Fluid and the Risk of PCOS Among Infertile Women: The Mediating Effect of Metabolic Markers - Xin Wang; Ying Zhang; Jie Peng; Hua Zhang; Tingting Jiang; Zhikang Zhang; Tao Yin; Xun Su; Tao Zhang; Lingchao Shen; Shitao He; Xiaolei Wang; et al. (Biological Trace Element Research, 2025)

Foxa1 disruption enhances human cell integration in human-mouse interspecies chimeras - Li-na Wang; Jun-shuang Jia; Xing-long Yang; Yue-ting Wen; Jing-xian Liu; Deng-ke Li; Xing-rui Chen; Jia-hong Wang; Ji-ke Li; Zhong-xi Huang; Kai-tai Yao (Cell and Tissue Research, 2025)

Spatiotemporal estimates and health risks of atmospheric trace metals across Hong Kong during 2016–2020 - Wenwen Sun; Shenghua Zhang; Dongmei Cai; Liqiang Wang; Ji Jin; Rui Li; Zhenghu Chen (Air Quality, Atmosphere & Health, 2025)

Cross‐Continental Shifts of Ecological Strategy in a Global Plant Invader - Ramona E. Irimia; Weihan Zhao; Peipei Cao; Madalin Parepa; Zhi‐Yong Liao; Shengyu Wang; Jeannie M. Mounger; Conner Richardson; Fatima Elkott; Xin Zhuang; Jingwen Bi; Jieren Jin; et al. (Global Ecology and Biogeography, 2025)
Aim Plant invasions are a global problem that requires studying plants and their environmental associations across native and introduced ranges. Location 2000 km transects in China, Europe and North America. Time Period June 2019–July 2020. Major Taxa Studied Japanese knotweed ( Reynoutria japonica ). Methods We surveyed 150 populations of Japanese knotweed, a noxious invader of the temperate zone, along 2000 km transects in native China and the introduced ranges of Europe and North America. Results We found that larger plants and denser populations in the introduced ranges were associated with shifts in leaf economy and chemical defences. Introduced knotweed populations had higher SLA but reduced leaf chlorophyll, lignin, C:N ratio and leaf toughness along with altered leaf tannins, flavonoids and alkaloids. We found three distinct multivariate knotweed phenotypes primarily in the introduced ranges, and two multivariate knotweed phenotypes mainly in native populations. Main Conclusions Decreased herbivore and pathogen impacts in introduced populations and changes in environmental associations indicate that enemy release and novel habitat conditions might have driven the emergence of novel ecological strategies in this global plant invader.

Dynamic Characteristics of Bidirectional Misaligned Marine Water-Lubricated Bearings Considering Turbulence, Surface Roughness and Bush Deformation - Ziqi Chen; Ji Wang; Rui Li; Yujun Liu (Journal of Marine Science and Engineering, 2025)
The marine water-lubricated bearing’s (WLBs) dynamic properties are essential for ensuring the shaft system’s operational dependability. The coupled model of mixed lubrication and turbulence under the impact of bidirectional misalignment is proposed in this research, and the perturbation equations of marine WLBs with 32 coefficients are derived. The finite difference method (FDM) is used to solve the steady-state and perturbation equations, and the impacts of turbulence, bearing bush deformation, surface roughness, and bidirectional shaft misalignment on the dynamic characteristics of the WLBs are systematically investigated. The results reveal that under mixed lubrication, surface roughness and the turbulence effect can both greatly improve the stiffness and damping of the bearings, but that there is a threshold phenomenon for the turbulence effect’s influence on these properties. Neglecting the elastic deformation of the bush may lead to an overestimation of the bearings’ stiffness and damping, causing substantial inaccuracies in conditions of heavy load or declined Young’s modulus. The 32 coefficients of the WLB exhibit considerable variation with the misalignment angle; hence, a more comprehensive dynamic model should be developed for misaligned marine WLBs. The study’s findings provide valuable insights for rotor dynamics research and optimal design of lubrication performance in marine WLBs.

Toward safe rice production in As-Cd co-contaminated paddy soils: Biogeochemical mechanisms and remediation strategies - Jing-Min Yang; Hui-Lin Chen; Xin Wang; Dong-Xing Guan; Xiong-Hui Ji; Yun-He Xie; Rui Huang; Bo Peng; Qin-Bo Qin (Critical Reviews in Environmental Science and Technology, 2025)

Utilizing large language models for identifying future research opportunities in environmental science - Xiaoliang Ji; Xinyue Wu; Rui Deng; Yue Yang; Anxu Wang; Ya Zhu (Journal of Environmental Management, 2025)

PET/CT-guided and OPN-targeted melanin nanoparticle platform for early diagnosis and precision therapy of idiopathic pulmonary fibrosis (IPF) - Jie Ji; Jie Sheng; Pengjun Zhang; Feng Wang; Yutong Xu; Xingyue Feng; Rui Xu; Yi Shen; Longjiang Zhang; Xiaodong Han (Chemical Engineering Journal, 2025)

Protective mechanism of antioxidant peptides derived from dry-cured ham against ultraviolet A-induced oxidative damage in HaCat cells - Rui-hong Xie; Shan Xiao; Da Ma; Bo Wang; Guan-chao Chen; Jun-han Xiang; Ji-hui Wang (Food Bioscience, 2024)

The remediation performance and mechanism for tetracycline from groundwater using controlled release materials containing mesoporous MnOx with different morphology - Ting Wang; Jing-le Chen; Rui Huang; Li-guang Wu; Kou-ping Chen; Ji-chun Wu; Hua-li Chen (Environmental Pollution, 2024)

Iron-doped diesel exhaust early-in-life inhalation-induced cardiopulmonary toxicity in chicken embryo: Roles of ferroptosis and acyl hydrocarbon signaling - Siyi Wang; Xinxian Gong; Junhua Yuan; Jing Huang; Rui Zhao; Jing Ji; Meinan Wang; Xiaoyu Shi; Wenya Xin; Yuxu Zhong; Yuxin Zheng; Qixiao Jiang (Environmental Pollution, 2024)

Highly stable zinc anodes enabled by a dual-function additive of in-situ film formation and electrostatic shielding - Rui-han Ji; Hao Fu; Qing Wen; Pei-Yao Li; Pei Yang; Yu-Jing Chen; He-zhang Chen; Jia-feng Zhang; Ling-jun Li; Jie-xi Wang; Qing Wu; Xia-hui Zhang; et al. (Chemical Engineering Journal, 2024)

A method for accurate extraction of three-dimensional point cloud feature data in loading test of container ships - Rui Li; Hexin Wan; Ji Wang; Shilin Huo; C. Guedes Soares (Ocean Engineering, 2024)

A novel 4-DOF marine stern bearing support model considering discrete distribution effects - Ziqi Chen; Ji Wang; Rui Li; Yujun Liu (Ocean Engineering, 2024)

Toxicity prediction and risk assessment of per- and polyfluoroalkyl substances for threatened and endangered fishes - Yuanpu Ji; Xiaolei Wang; Rui Wang; Jiayu Wang; Xiaoli Zhao; Fengchang Wu (Environmental Pollution, 2024)

Straw return can increase maize yield by regulating soil bacteria and improving soil properties in arid and semi-arid areas - Xiaoling Wang; Rui Qian; Yafang Han; Zhe Ji; Qingxuan Yang; Longlong Wang; Xiaoli Chen; Kun Ma; Kadambot H.M. Siddique; Zhikuan Jia; Xiaolong Ren (European Journal of Agronomy, 2024)

Metasedimentary “carbon filter” and its implication for subduction zone carbon recycling - Ji-Lei Li; E.M. Stewart; Timm John; Jay J. Ague; Zhong-Rui Wang; Zhi-Pei Ma; Jun Gao (Earth and Planetary Science Letters, 2024)

Delaying cyclization of polyacrylonitrile by boric acid for sulfurized poly(acrylonitrile) cathode materials - Xuan Zhang; Hui-Chao Lu; Chen-Ran Hao; Ji-Qiong Liu; Xi-Rui Kong; Jiu-Lin Wang (Chemical Engineering Journal, 2024)

Enhanced photocatalytic Cr(VI) degradation and real-time detection using dual-fluorescent quantum dot-infused polysulfone microspheres - Rui Zhao; Feihong Hu; Shan Li; Chao Liu; Zhiwei Wang; Zhaoping Song; Dandan Ji; Xiaona Liu; Huili Wang; Wenxia Liu; Fengshan Zhang; Dehai Yu (Journal of Environmental Chemical Engineering, 2024)

Ultrasound-responsive ZnS:Ag QDs loaded TiO2 biointerfaces: In situ sonodynamic antimicrobial therapy for biomedical implants - Lei Ji; Yun Xue; Dong Wang; Yu Fan; You Zhou; Chuanan Shen; Rui Shi; Jiatao Zhang (Chemical Engineering Journal, 2024)

Extracellular vesicles in pulmonary infection: From pathophysiology to theranostic technologies - Xu Wang; Mai-Qing Shi; Yang Wang; Hao Zhou; Ke Peng; Jun Wang; Shi-Kun Sun; Xu-Rui Shen; Jia-Jia Wang; Zhi Zhao; Xian-Guang Ding; Fu-Hai Ji (Chemical Engineering Journal, 2024)

Advances in the Differentiation of hiPSCs into Cerebellar Neuronal Cells - Yingxin Wang; Wenzhu Liu; Yichang Jiao; Yitong Yang; Didi Shan; Xinbo Ji; Rui Zhang; Zexin Zhan; Yao Tang; Dandan Guo; Chuanzhu Yan; Fuchen Liu (Stem Cell Reviews and Reports, 2024)

Chemical constituents from the aerial parts of Rhododendron thymifolium and its bioactivities against Tribolium castaneum, Lasioderma serricorne, and Ditylenchus destructor - Jun-Yu Liang; Ying-Ying Yang; Rui Feng; Xiao-Han Zhang; Xu-Dong Wang; Jun-Long Wang; Wei-Bao Kong; Ji Zhang (Journal of Plant Diseases and Protection, 2024)

Iron Level in Pregnant Rats is Associated with Caries Susceptibility in Offsprings - Jun Lu; Shuaiqi Ji; Lei Ma; Yanhui Wang; Yongliang Wang; Jin Yue; Rui Han (Biological Trace Element Research, 2024)

Assessing the preservation of orbital signals across different sedimentary environments: Insights from stochastic sedimentation modeling - Meng Wang; Mingsong Li; Elizabeth A. Hajek; David B. Kemp; Yujing Wu; Hanyu Zhu; Chunju Huang; Haotian Zhang; Kaixuan Ji; Rui Zhang; Ren Wei; Zhijun Jin (Earth and Planetary Science Letters, 2024)

Wearable hydrogel-based health monitoring systems: A new paradigm for health monitoring? - Xintao Wang; Haixia Ji; Li Gao; Rui Hao; Ying Shi; Junyan Yang; Yuan Hao; Jiahui Chen (Chemical Engineering Journal, 2024)

Phase I clinical trial of intracerebral injection of lentiviral-ABCD1 for the treatment of cerebral adrenoleukodystrophy - Qiu-Hong Wang; Jing Wang; Zhi-Pei Ling; Zhi-Qiang Cui; Jie Gong; Rui Zhang; Shi-Jun Li; Yang-Yang Wang; Rui Yang; De-Hui Huang; Wen He; Jing Gao; et al. (Science Bulletin, 2024)

The mitigation of citric acid on cadmium toxicity in Iris tectorum and its effects on the composition of cell walls - Xiao-Fang Yu; Zhi-Wen Wang; Feng-Lian Chen; Mao-Lin Chen; Xin-Yu Zhang; Jun-Rui Zhang; Wen-Yu Ji; Xue Xiao; Li-Juan Yang; Ting Lei; Xi Li; Ming-Yan Jiang (International Biodeterioration & Biodegradation, 2024)

Gas chromatography-mass spectrometry and non-targeted metabolomics analysis reveals the flavor and nutritional metabolic differences of cow's milk fermented by Lactiplantibacillus plantarum with different phenotypic - Xueliang Zhang; Changliang Zhang; Luyao Xiao; Xiaochan Wang; Kai Ma; Feng Ji; Elham Azarpazhooh; Marjan Ajami; Xin Rui; Wei Li (Food Bioscience, 2024)

Rapid differential diagnosis of periprosthetic joint infection by microdroplet reaction on portable biochip and indicator - Zheng Liu; Jimei Chi; Zewei Lian; Yaqi Yang; Lijun Cheng; Xiaoxue Lin; Xuwei He; Xiaojian Ji; Chenxuan Yang; Yunhao Tang; Minzhi Yang; Zhisen Gao; et al. (Chemical Engineering Journal, 2024)

Highly nanostructured and carboxylated wood aerogel-based adsorption membrane reconstructed by grafting of polyacrylic acid for efficient removal of heavy-metal ions - Wen He; Bairen Wei; Shuang Liang; Rui Wang; Qiulin Ji; Gangzheng Hu; Wenxuan Li; Lei He; Juan Yu; Hongfei Zhu; Kaiyin Wang (Chemical Engineering Journal, 2024)

Diversity and environmental determinants of aquatic plants across China - Mengtian Ji; Rui Dong; Junhui Zhang; Xinlei Shi; Yuchao Wang; Qiqi Huang; Dan Qu; Yuyu Wang (Hydrobiologia, 2024)

Repetitive Transcranial Magnetic Stimulation-Mediated Neuroprotection in the 5xFAD Mouse Model of Alzheimer’s Disease Through GABRG2 and SNAP25 Modulation - Jinyang Wang; Chenming Zhou; Zhimin Huang; Xiaoming Ji; Rui Cui; Yunxiao Kang; Guoliang Zhang; Yu Wang; Tianyun Zhang (Molecular Neurobiology, 2024)

Quercetin regulates dendritic cell activation by targeting STAT4 in the treatment of experimental autoimmune encephalomyelitis - Fang Zhou; Yu-Xin Guo; Rui Gao; Xiao-Yu Ji; Yu-Xuan Tang; Li-Bin Wang; Yuan Zhang; Xing Li (Toxicology and Applied Pharmacology, 2024)

Separation, enrichment and cytoprotection of antioxidant peptides from Xuanwei ham using aqueous two-phase extraction - Rui-hong Xie; Shan Xiao; Xuan Chen; Bo Wang; Yao-yao Hu; Ji-hui Wang (Food Chemistry, 2024)

Efficient nitrogen removal from mainstream sewage in tidal flow constructed wetlands: Targeted migration and conducive spatial distribution for pollutants removal - Rui Ma; Caocong Liu; Yiyuan Zhuo; Jiangsen Ma; Linsong Cheng; Fangying Ji; Xiaoming Wang (Chemical Engineering Journal, 2024)

The Association Between the Levels of Oxidative Stress Indicators (MDA, SOD, and GSH) in Seminal Plasma and the Risk of Idiopathic Oligo-asthenotera-tozoospermia: Does Cu or Se Level Alter the Association? - Tao Yin; Xinyu Yue; Qian Li; Xinyu Zhou; Rui Dong; Jiayi Chen; Runtao Zhang; Xin Wang; Shitao He; Tingting Jiang; Fangbiao Tao; Yunxia Cao; et al. (Biological Trace Element Research, 2024)

Research on the effect of shallow draft on the performance of azimuth thruster under bollard conditions - Heng Li; Jian-Qiang Wang; Xue-Qin Liu; Guo-Rui Ji; Yan Zhang; Zhi-Yuan Wei (Ocean Engineering, 2024)

Degradation of quinolone antibiotics by freeze activated periodate: effect of the number of fluorine substituents and DFT calculations - Hao Lin; Yan Zhang; Yucan Liu; Xiuping Sun; Bin Ji; Rui Mei; Tongshuai Liu; Zhonglu Gao; Xin Wang (Journal of Environmental Chemical Engineering, 2024)

Lotus pollen-derived nitrogen and phosphorus self-doped TiO2/carbon materials for photoelectrochemical application - Rui Chen; Ying-Ying Wang; Xia Jiang; Ming-Hao Ji; Ke-Xian Li; Hao-Yan Shi; Hai-Long Wang; Yan-Xin Chen; Can-Zhong Lu (Journal of Environmental Chemical Engineering, 2024)

Low temperature catalytic activity of molybdenum promoted two-dimensional boron nitride in propane oxidative dehydrogenation reaction - Yixiang Zhu; Rui Chen; Yixuan Yang; Yu Liu; Xuyu Wang; Hongbing Ji (Chemical Engineering Journal, 2024)

Temperature-driven dynamic evolution process of Ag species on silver-loaded Zr0.2Sn0.8O2 catalyst for selective catalytic oxidation of ammonia - Yan Zhang; Zongxiang Yang; Meng Wang; Min Zhang; Caixia Liu; Qingling Liu; Weichao Wang; Ziyin Zhang; Rui Han; Na Ji (Chemical Engineering Journal, 2024)

Exogenous application of salicylic acid improves eradication of apple stem grooving virus and apple chlorotic leaf spot virus in apple - Xiao-Yan Ma; Jin-Wei Li; Qing Li; Zi-Han Yan; Xi Cheng; Min-Rui Wang; Zhibo Hamborg; Lu Bao; Dong Zhang; Min-Ji Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Evaluating the fracture resistance and drainage difficulty of coal reservoirs using log data - Zhi-di Liu; Bin-rui Yang; Xiao-yan Tang; Wei Wang; Liang Ji; Zhi-hao Jiang (Applied Geophysics, 2024)

Encapsulate Co3O4 within ultrathin graphene sheets to enhance peroxymonosulfate activation by tuning surface electronic structures - Taobo Huang; Rui An; Jie Li; Wen Liu; Xiuping Zhu; Haodong Ji; Ting Wang (Science of The Total Environment, 2024)

Synergistic effects of chemical additives and mature compost on reducing H2S emission during kitchen waste composting - Yongdi Liu; Haihou Wang; Hao Zhang; Yueyue Tao; Rui Chen; Sheng Hang; Xiaoyan Ding; Meidi Cheng; Guochun Ding; Yuquan Wei; Ting Xu; Ji Li (Journal of Environmental Sciences, 2024)

Comparative study of reactive oxygen species and tetracycline degradation pathways in catalytic peroxodisulfate activation by asymmetric mesoporous TiO2 and the corresponding controlled-release materials - Ting Wang; Rui Huang; Hua-Li Chen; Kun-Miao Xu; Li-Guang Wu; Kou-Ping Chen; Ji-Chun Wu (Environmental Pollution, 2024)

Insights into the Degradation and Mechanism of the Enhanced Persulfate Degradation of Tetracycline using an Efficient 3D Copper Metal–Organic Frameworks - Rui Zhou; Congyang Zou; Yong Wang; Zhuyou Zhou; Menghe Liu; Yufeng Ji (Water, Air, & Soil Pollution, 2024)

Non-fitting functional representation for the equilibrium constant subject to reaction between H2S and CO2 - Chao-Wen Wang; Ji Li; Lie-Hui Zhang; Qun-Chao Ding; Guan-Hong Liu; Gao Li; Rui Jiang; Xiao-Long Peng; Lin-Sheng Wei; Hong-Ming Tang; Jian-Yi Liu; Chun-Sheng Jia (Fuel, 2024)

Effect of berry-derived phenolic products on blood lipid profiles: A systematic review and meta-analysis - Chunxiao Ji; Rui Wang; Dongliang Wang; Yongle Luo; Zaiming Huang; Jianying Liu; Anwei Cheng (Food Bioscience, 2024)

A triggered DNA nanomachine with enzyme-free for the rapid detection of telomerase activity in a one-step method - Huajie Pang; Yanan Peng; Rui Zhang; Zhijun Gao; Xiangde Lai; Dongxia Li; Xuan Zhao; Yuanyuan Wang; Hua Pei; Bin Qiao; Yuxiang Ji; Qiang Wu (Analytica Chimica Acta, 2024)

Numerical calculation of overlapping line heating for marine titanium alloy curved plate - Shun Wang; Jiayan Wang; Zhikang Xu; Ji Wang; Rui Li (Ocean Engineering, 2024)

Effects of κ-carrageenan on the emulsifying ability and encapsulation properties of pea protein isolate-grape seed oil emulsions - Wenjuan Wang; Rui Sun; Suping Ji; Qiang Xia (Food Chemistry, 2024)

Promotion of anaerobic biodegradation of azo dye RR2 by different biowaste-derived biochars: Characteristics and mechanism study by machine learning - Yu-Qian Wang; Jie Ding; Ji-Wei Pang; Chuan-Dong Wu; Han-Jun Sun; Rui Fang; Nan-Qi Ren; Shan-Shan Yang (Bioresource Technology, 2024)

Numerical study on uplift capacity and behavior of plate anchor considering different dilation angles - Yong-sheng Wang; Wei Ye; Hao Liu; Quanping Gao; Ji-xin Li; Rui-heng Ding; Rui Rui (Arabian Journal of Geosciences, 2024)

Ubiquitination-dependent protein homeostasis is critical for the thermotolerance of the economically valuable seaweed Pyropia haitanensis - Rui Zhao; Jian Wen; Kai Xu; Yan Xu; Dehua Ji; Chaotian Xie; Wenlei Wang (Aquaculture, 2024)

PD-L1 expression guidance on sintilimab versus pembrolizumab with or without platinum-doublet chemotherapy in untreated patients with advanced non-small cell lung cancer (CTONG1901): A phase 2, randomized, controlled trial - Si-Yang Maggie Liu; Jie Huang; Jia-Yi Deng; Chong-Rui Xu; Hong-Hong Yan; Ming-Yi Yang; Yang-Si Li; E-E Ke; Ming-Ying Zheng; Zhen Wang; Jia-Xin Lin; Bin Gan; et al. (Science Bulletin, 2024)

Salvirrane A-F, six undescribed nordrimane sesquiterpene derivatives from Salvia castanea Diels f. tomentosa Stib and their cytotoxic activities - Rui Zhang; Dong-Dong Wang; Lian-Yu Tang; Peng-Xue Ji; Xin-Min Li; Zi-Feng Guo; Jue Wang; Jing-Ming Jia; An-Hua Wang (Phytochemistry, 2024)

Path following of QAUV using attitude-velocity coupling model - Daxiong Ji; Rui Wang (Ocean Engineering, 2024)

Deformation Intelligent Prediction of Titanium Alloy Plate Forming Based on BP Neural Network and Sparrow Search Algorithm - Shun Wang; Jiayan Wang; Zhikang Xu; Ji Wang; Rui Li; Jinliang Dai (Journal of Marine Science and Engineering, 2024)
The application of titanium alloy in shipbuilding can reduce ship weight and carbon emissions. To solve the problem of titanium alloy forming, the deformation prediction of titanium alloy line heating based on a backpropagation (BP) neural network and sparrow search algorithm (SSA) was researched. Based on the thermal–elastic–plastic finite element method, the numerical calculation model of TA5 titanium alloy overlapping heating forming was established. The feasibility of the model was verified by comparing it with the numerical calculation and experiment of low-carbon steel. Considering the characteristics of the titanium alloy-forming process, 73 groups of titanium alloy-forming schemes were obtained by the Latin hypercube sampling method. The deformation data of the samples were obtained by using the numerical calculation model of titanium alloy forming. The prediction methods of titanium alloy-forming deformation based on BP, genetic algorithm–backpropagation (GA-BP), and SSA-BP were proposed. The accuracy of different neural network prediction models was analyzed. The mean absolute percentage errors (MAPEs) of BP, GA-BP, and SSA-BP in shrinkage prediction were 7.45%, 4.08%, and 2.96%, respectively. The MAPEs of BP, GA-BP, and SSA-BP in deflection prediction were 8.44%, 4.73%, and 2.64%, respectively. The goodness of fit (R2) of SSA-BP is closest to 1 among the three models. The calculation results show that SSA-BP is better than BP and GA-BP in predicting the forming deformation of titanium alloy. The maximum prediction error of SSA-BP is 4.95%, which is within the allowable range of engineering error. The SSA-BP prediction model is suitable for the rapid and accurate prediction of the deformation of titanium alloy line heating forming. The intelligent prediction model provides data support for intelligent decisions for titanium alloy forming.

Comparison of the ozone formation mechanisms and VOCs apportionment in different ozone pollution episodes in urban Beijing in 2019 and 2020: Insights for ozone pollution control strategies - Yunfeng Li; Zhenhai Wu; Yuanyuan Ji; Tianshu Chen; Hong Li; Rui Gao; Likun Xue; Yafei Wang; Yuxi Zhao; Xin Yang (Science of The Total Environment, 2024)

A review of the strategy to promote microalgae value in CO2 conversion-lipid enrichment-biodiesel production - Huan Liu; Tian-Ji Liu; Hua-Wei Guo; Ya-Jun Wang; Rui Ji; Le-Le Kang; Yi-Tong Wang; Xuan Guo; Jun-Guo Li; Li-Qun Jiang; Zhen Fang (Journal of Cleaner Production, 2024)

Human activity and climate change accelerate the extinction risk to non‐human primates in China - Wen‐Bo Li; Yang Teng; Ming‐Yi Zhang; Ying Shen; Jia‐Wen Liu; Ji‐Wei Qi; Xiao‐Chen Wang; Rui‐Feng Wu; Jin‐Hua Li; Paul A. Garber; Ming Li (Global Change Biology, 2024)
Human activity and climate change affect biodiversity and cause species range shifts, contractions, and expansions. Globally, human activities and climate change have emerged as persistent threats to biodiversity, leading to approximately 68% of the ~522 primate species being threatened with extinction. Here, we used habitat suitability models and integrated data on human population density, gross domestic product (GDP), road construction, the normalized difference vegetation index (NDVI), the location of protected areas (PAs), and climate change to predict potential changes in the distributional range and richness of 26 China's primate species. Our results indicate that both PAs and NDVI have a positive impact on primate distributions. With increasing anthropogenic pressure, species' ranges were restricted to areas of high vegetation cover and in PAs surrounded by buffer zones of 2.7–4.5 km and a core area of PAs at least 0.1–0.5 km from the closest edge of the PA. Areas with a GDP below the Chinese national average of 100,000 yuan were found to be ecologically vulnerable, and this had a negative impact on primate distributions. Changes in temperature and precipitation were also significant contributors to a reduction in the range of primate species. Under the expected influence of climate change over the next 30–50 years, we found that highly suitable habitat for primates will continue to decrease and species will be restricted to smaller and more peripheral parts of their current range. Areas of high primate diversity are expected to lose from 3 to 7 species. We recommend that immediate action be taken, including expanding China's National Park Program, the Ecological Conservation Redline Program, and the Natural Forest Protection Program, along with a stronger national policy promoting alternative/sustainable livelihoods for people in the local communities adjacent to primate ranges, to offset the detrimental effects of anthropogenic activities and climate change on primate survivorship.

New insight into the pyrophoricity and mechanism of ironic sulfide from synergistic effect of FeS and FeS2 - Kai Pan; Hui Liu; Zhihui Lang; Rui Huang; Ze Wei; Wenjing Ji; Jianhai Wang; Dong Ye; Haining Wang (Fuel, 2023)

The interaction among Kluyveromyces marxianus G-Y4, Lacticaseibacillus paracasei GL1, and Lactobacillus helveticus SNA12 and signaling molecule AI-2 participate in the formation of biofilm - Xiaomeng Wang; Kai Ma; Changliang Zhang; Feng Ji; Lili Chen; Xueliang Zhang; Ghahvechi Chaeipeima Mahsa; Elham Azarpazhooh; Marjan Ajami; Xin Rui; Wei Li (Food Microbiology, 2023)

A review of starch swelling behavior: Its mechanism, determination methods, influencing factors, and influence on food quality - Ruoyu Jia; Congli Cui; Lin Gao; Yang Qin; Na Ji; Lei Dai; Yanfei Wang; Liu Xiong; Rui Shi; Qingjie Sun (Carbohydrate Polymers, 2023)

Comparison of demineralized bone matrix with different cycling crushing times in posterolateral fusion model of athymic rats - Shao-Lin Ji; Xiao-Dan Zhao; Li-Min Wang; Cheng-Gang Pang; Wen-Jing Li; Kun-Xiu Song; Rong-Xing Ma; Rui-Feng Li; Jing-Yu Zhang; Yong-Cheng Hu (Cell and Tissue Banking, 2023)

A Pre-Procession Module for Point-Based Deep Learning in Dense Point Clouds in the Ship Engineering Field - Shilin Huo; Yujun Liu; Ji Wang; Rui Li; Xiao Liu; Jiawei Shi (Journal of Marine Science and Engineering, 2023)
Recently, point cloud technology has been applied in the ship engineering field. However, the dense point cloud acquired by terrestrial laser scanning (TLS) technology in ship engineering applications brings an obstacle to some powerful and advanced point-based deep learning point cloud processing methods. This paper presents a deep learning pre-procession module to ensure the feasibility of processing dense point clouds on commonly available computer devices. The pre-procession module is designed according to the traditional point cloud processing methods and the PointNet++ paradigm, and is evaluated on two ship structure datasets and two popular point cloud datasets. Experimental results illustrate that (i) the proposed module improves the performance of point-based deep learning semantic segmentation networks, and (ii) the proposed module empowers the existing point-based deep learning networks with the capability to process dense input point clouds. The proposed module may provide a useful semantic segmentation tool for realistic dense point clouds in various industrial applications.

The hepatoprotective effects of plant-based foods based on the “gut–liver axis”: a prospective review - Qiongdan Hu; Wan Liao; Zhen Zhang; Sanjun Shi; Shuguang Hou; Ningping Ji; Xinjie Zhang; Qian Zhang; Yangyang Liao; Linghui Li; Zongping Zhu; Yi Chen; et al. (Critical Reviews in Food Science and Nutrition, 2023)

Enhanced As extraction from paddy soils with high As contamination risk by rice plant upon Si fertilization - Rui Huang; Xin Wang; Wei Wei; Yunhe Xie; Saihua Liu; Haoyu Chen; Renjie Zhang; Xionghui Ji (Chemosphere, 2023)

Developmental and neurobehavioral toxicity of 2,2′-methylenebis(6-tert-butyl-4-methylphenol) (antioxidant AO2246) during the early life stage of zebrafish - Yinan Chai; Donglai Sheng; Xiaowei Ji; Yanlong Meng; Feihao Shen; Rui He; Runjia Ma; Yuying Wang (Science of The Total Environment, 2023)

Experimental study on enhanced coal seam gas extraction by uniform pressure/pulse pressure N2 injection - Peng-fei Ji; Hai-fei Lin; Xiang-guo Kong; Shu-gang Li; Yu-chu Cai; Rui-zhe Wang; Yu Tian; Tian-shuo Zhao (Fuel, 2023)

Epithelial lining inspired protective shield for prolonged endotracheal intubation - Baisong Zhao; Meng-Han Bai; Luxi Zhang; Qingning Wang; Yongying Pan; Yan-Pu Li; Rui Hong; Juxiang Gou; Dongjie Zhang; Yuwei Liu; Gan-Ji Zhong; Ka Li; et al. (Chemical Engineering Journal, 2023)

Multiple stages of Au mobilization in the Changshagou Au deposit, Eastern Tianshan, NW China: Insights from mineral chemistry and fluid inclusions - Yi-Hao Liu; Yun Zhao; Chun-Ji Xue; Rui Wang; Hai-Xia Chu; Xiao-Bo Zhao; Matthew J. Brzozowski; Reimar Seltmann; Jun Chen; Jun-Bao Gao (Journal of Asian Earth Sciences, 2023)

Effects of Lactiplantibacillus plantarum with different phenotypic features on the nutrition, flavor, gel properties, and digestion of fermented soymilk - Xueliang Zhang; Changliang Zhang; Luyao Xiao; Suying Wang; Xiaochan Wang; Kai Ma; Feng Ji; Elham Azarpazhooh; Marjan Ajami; Xin Rui; Wei Li (Food Bioscience, 2023)

Astragaloside IV-mediated inhibition of oxidative stress by upregulation of ghrelin in type 2 diabetes–induced cognitive impairment - Rui-hua Zhang; Shan-shan Cao; Yong Shi; Xin Wang; Lei-lei Shi; Yu-han Zhang; Chao-jun Han; Bin Wang; Liang Feng; Ji-ping Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Regeneration of high-performance materials for electrochemical energy storage from assorted solid waste: A review - Jia-feng Zhang; De-zhao Peng; Xiang-gang Gao; Jing-tian Zou; Long Ye; Guan-jun Ji; Bi Luo; Gui-hui Yu; Peng-fei Li; Xiao-wei Wang; Zao-wen Zhao; Bao Zhang; et al. (Journal of Cleaner Production, 2023)

Insights on rational design and regulation strategies of Prussian blue analogues and their derivatives towards high-performance electrocatalysts - Yu-Rui Ji; Ya-Fei Guo; Xu Liu; Peng-Fei Wang; Ting-Feng Yi (Chemical Engineering Journal, 2023)

Efficient lipid synthesis of Chlorella pyrenoidosa promoted under heavy metals from electric arc furnace slag - Qing Yu; Tian-Ji Liu; Ya-Nan Zeng; Yi-Tong Wang; Jun-Guo Li; Yu-Ran Wang; Le-Le Kang; Rui Ji; Fu-Ping Wang; Xiao-Man Wang; Bao Liu; Shuang Cai; et al. (Journal of Cleaner Production, 2023)

Preparation, characterization, and evaluation of tamarind seed polysaccharide-carboxymethylcellulose buccal films loaded with soybean peptides-chitosan nanoparticles - Suping Ji; Rui Sun; Wenjuan Wang; Qiang Xia (Food Hydrocolloids, 2023)

Degradation of trichloroethylene by double dielectric barrier discharge (DDBD) plasma technology: Performance, product analysis and acute biotoxicity assessment - Xu-Rui Hu; Yong-Chao Wang; Zhen Tong; Can Wang; Er-Hong Duan; Meng-Fei Han; Hsing-Cheng Hsi; Ji-Guang Deng (Chemosphere, 2023)

Study on the Methods of Measurement, Optimization and Forecast of Propulsion Shaft Bearing Load of Ships - Rui Li; Ji Wang; Ziqi Chen; Feixiang Wang; Yujun Liu (Journal of Marine Science and Engineering, 2023)
The qualit12y of shafting alignment is related to the reliability and safety of a ship’s operation, and bearing displacement adjustment (BDA) plays a key role in shafting alignment. To solve the problems encountered in ship shafting alignment in the actual construction, this study focused on the investigation of the shafting load measurement system based on the strain gauge method (SGM), used the optimization method based on quadratic programming (QP) to calculate the BDA and adopted algorithms based on the bearing load influence coefficients (BICs) to forecast the load after the adjustment. The experimental work, as well as the measurement, calculation and analysis of several real ships, indicated that the measurement, optimization and forecasting methods of the bearing load of the propulsion shafting of large ships in this study would be significant for guiding the actual construction work of ship shafting alignment.

Subassembly Partition of Hull Block Based on Two-Dimensional PSO Algorithm - Bo Liu; Rui Li; Ji Wang; Yujun Liu; Sheng Li (Journal of Marine Science and Engineering, 2023)
Subassembly partition is an important process in hull block building as it greatly affects the efficiency and quality of the assembly work. Recently, an experience-based method has been widely applied to the subassembly partition process, which consumes much design time and manpower, thus causing more challenges toward a more highly automated and efficient stage in this process. To shorten the gap, an automated subassembly partition method is presented in this study. First, the assembly information model is defined with essential attributes and topological relations of the parts. Second, an optimization model is established with consideration of a trade-off between the intra-cluster cohesion and cluster number on the premise of satisfying certain constraints. After that, considering the fuzziness and diversity of the subassembly partition problem, a two-dimensional coding discrete particle swarm optimization (PSO) algorithm is developed. Finally, two blocks are demonstrated as instances to verify the proposed method, and the results show that the proposed method is feasible and applicable to the block with a flat structure.

Hormesis effects of sulfoxaflor on Aphis gossypii feeding, growth, reproduction behaviour and the related mechanisms - Li Wang; Junshu Zhu; Qinqin Wang; Xuejiao Ji; Wenjie Wang; Weiling Huang; Changhui Rui; Li Cui (Science of The Total Environment, 2023)

High magnesian schist, granitic gneiss, amphibolite and monzogneiss in the eastern Ama Drime Massif in South Tibet (China): A rifted Paleoproterozoic arc fringed the western Columbia supercontinent? - Rui Li; Wenjiao Xiao; Qigui Mao; Ji'en Zhang; Songjian Ao; Dongfang Song; Zhou Tan; Hao Wang; Saunak Bhandari (Precambrian Research, 2023)

Structural incorporation of iron influences biomethylation potential of mercury sulfide - Yunyun Ji; Shan Gao; Rui Si; Zhanhua Zhang; Li Tian; Wenyu Guan; Weichao Wang; Jiubin Chen; Wei Chen; Pedro J.J. Alvarez; Tong Zhang (Geochimica et Cosmochimica Acta, 2023)

Preparation and characterization of V-type starch nanoparticles by an oil-water interface method - Hao Lu; Xiaoyang He; Yang Qin; Na Ji; Lei Dai; Liu Xiong; Rui Shi; Tao Wang; Qingjie Sun (Food Hydrocolloids, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

A20 ameliorates disc degeneration by suppressing mTOR/BNIP3 axis-mediated mitophagy - Xin Peng; Cong Zhang; Jia-Wei Gao; Feng Wang; Jun-Ping Bao; Zhi-Min Zhou; Rui Sun; Hang-Yu Ji; Cabral VLF; Xiao-Tao Wu (Genes & Genomics, 2023)

Sulfoxaflor adversely influences the biological characteristics of Coccinella septempunctata by suppressing vitellogenin expression and predation activity - Li Wang; Yanhui Zhai; Junshu Zhu; Qinqin Wang; Xuejiao Ji; Wenjie Wang; Huizhu Yuan; Changhui Rui; Li Cui (Journal of Hazardous Materials, 2023)

Long-term performance analysis of BDS-3 precise point positioning (PPP-B2b) service - Shuang Sun; Min Wang; Changjian Liu; Xin Meng; Rui Ji (GPS Solutions, 2023)

Characteristics, sources and health risk assessment of atmospheric carbonyls during multiple ozone pollution episodes in urban Beijing: Insights into control strategies - Yunfeng Li; Hong Li; Xin Zhang; Yuanyuan Ji; Rui Gao; Zhenhai Wu; Manfei Yin; Lei Nie; Wei Wei; Guohao Li; Yafei Wang; Mei Luo; et al. (Science of The Total Environment, 2023)

Reduced plastic film mulching under zero tillage boosts water use efficiency and soil health in semiarid rainfed maize field - Ai-Tian Ren; Ji-Yuan Li; Ling Zhao; Rui Zhou; Jian-Sheng Ye; Yi-Bo Wang; Xu-Cheng Zhang; Kiprotich Wesly; Ming-Sheng Ma; You-Cai Xiong (Resources, Conservation and Recycling, 2023)

Upcycling corn straw into nanocelluloses via enzyme-assisted homogenization: Application as building blocks for high-performance films - Hongbin Yang; Long Bai; Yaxin Duan; Hongxiang Xie; Xumei Wang; Rui Zhang; Xingxiang Ji; Chuanling Si (Journal of Cleaner Production, 2023)

The circadian regulation of extracellular ATP - Xin Wang; Yu-Ting Dong; Xiu-Ming Hu; Ji-Zhou Zhang; Nan-Rui Shi; Yan-Qin Zuo; Xu Wang (Purinergic Signalling, 2023)
Extracellular ATP is a potent signaling molecule released from various cells throughout the body and is intimately involved in the pathophysiological functions of the nervous system and immune system by activating P2 purinergic receptors. Recent increasingly studies showed that extracellular ATP exhibits circadian oscillation with an approximately 24-h periodicity, which participates in regulatory pathways of central oscillator suprachiasmatic nucleus and peripheral oscillator bladder, respectively. Oscillators modulate the protein expression of ATP release channels and ectonucleotidase activity through clock genes; indeed, real-time alterations of ATP release and degradation determine outcomes of temporal character on extracellular ATP rhythm. The regulatory pathways on extracellular ATP rhythm are different in central and peripheral systems. In this review, we summarize the circadian rhythm of extracellular ATP and discuss several circadian regulatory pathways in different organs via ATP release and degradation, to provide a new understanding for purinergic signaling in the regulatory mechanism of circadian rhythm and a potential target to research the circadian regulation of extracellular ATP in other circadian oscillators.

P2Y12 receptor gene polymorphisms are associated with epilepsy - Qi Wang; Nan-Rui Shi; Peng Lv; Juan Liu; Ji-Zhou Zhang; Bin-Lu Deng; Yan-Qin Zuo; Jie Yang; Xin Wang; Xiang Chen; Xiu-Min Hu; Ting-Ting Liu; et al. (Purinergic Signalling, 2023)
The basic research indicated that microglial P2Y12 receptors ( P2Y12Rs ) are involved in the pathophysiology of epilepsy through regulated microglial-neuronal interactions, aberrant neurogenesis, or immature neuronal projections. However, whether the clinic case of epilepsy would be associated with P2Y12 receptor gene polymorphisms is presented with few data. In our study, a total of 176 patients with epilepsy and 50 healthy controls were enrolled. Two single-nucleotide polymorphisms, namely rs1491974 and rs6798347, were selected for analysis. The results revealed that carriers of the G allele of rs1491974 G>A or rs6798347 G>A may be associated with an increased risk of epilepsy (OR = 0.576, 95% CI = 0.368–0.901, p = 0.015; OR = 0.603, 95% CI = 0.367–0.988, p = 0.043). Interestingly, we found that the rs1491974 G>A genotype and allele frequencies have only a significant difference in female instead of male case ( p = 0.004 for genotype; p = 0.001 for allele). The subgroup analysis demonstrated that individuals with the rs1491974 G>A genotype might have more frequent seizure (OR = 0.476, 95% CI = 0.255–0.890; p = 0.019). These data implied that both rs1491974 and rs6798347 polymorphisms of P2Y12R would be able to play import roles in epilepsy susceptibility, whereas the rs1491974 polymorphism may be specifically related to seizure frequency.

Phytoplankton biomass dynamics with diffuse terrestrial nutrients pollution discharge into bay - Wei Ouyang; Rui Wang; Kaiyue Ji; Xitao Liu; Fang Geng; Xin Hao; Chunye Lin (Chemosphere, 2023)

The physicochemical properties of a starch–sodium stearoyl lactylate complex formed via annealing treatment in ethanol solutions - Xiaoyu Chen; Chaofan Wang; Xiaoyang He; Yang Qin; Lei Dai; Liu Xiong; Tao Wang; Rui Shi; Na Ji; Qingjie Sun (Food Hydrocolloids, 2023)

Facilitating both anionic and cationic redox processes in Na-rich layered cathode materials by heteroatomic doping - Ziwei Chen; Maolin Yang; Zhongyuan Huang; Yanda Fu; Zhefeng Chen; Simo Li; Minzhi zhan; Rui Wang; Mihai Chu; Rui Qi; Xing Cheng; Zhewen Ma; et al. (Chemical Engineering Journal, 2023)

TREM2 and Microglia Contribute to the Synaptic Plasticity: from Physiology to Pathology - Chao-Ji Yu; Meng Wang; Rui-Yang Li; Tao Wei; Han-Chen Yang; Yun-Si Yin; Ying-Xin Mi; Qi Qin; Yi Tang (Molecular Neurobiology, 2023)

Study on the trajectory of tip leakage vortex and energy characteristics of mixed-flow pump under cavitation conditions - Wei Li; Mingjiang Liu; Leilei Ji; Shuo Li; Rui Song; Cheng Wang; Weidong Cao; Ramesh K. Agarwal (Ocean Engineering, 2023)

Phytochemical and underlying mechanism of Mikania micrantha Kunth on antibiotic resistance genes, and pathogenic microbes during chicken manure composting - Yousif Abdelrahman Yousif Abdellah; Yu-Sen Luo; Shan-Shan Sun; Xi Yang; Hong-Yi Ji; Rui-Long Wang (Bioresource Technology, 2023)

Solar ring mission: Building a panorama of the Sun and inner-heliosphere - Yuming Wang; Xianyong Bai; Changyong Chen; Linjie Chen; Xin Cheng; Lei Deng; Linhua Deng; Yuanyong Deng; Li Feng; Tingyu Gou; Jingnan Guo; Yang Guo; et al. (Advances in Space Research, 2023)

Highly efficient removal of hexavalent chromium by magnetic Fe–C composite from reed straw and electric furnace dust waste - Fu-Ping Wang; Ya-Nan Zeng; Yi-Tong Wang; Jun-Guo Li; Xi Zhang; Ai-Min Ji; Le-Le Kang; Rui Ji; Qing Yu; Di Gao; Xiao-Man Wang; Zhen Fang (Environmental Science and Pollution Research, 2022)

Efficacy and Safety of Recombinant Human Prourokinase in Acute Ischemic Stroke: A Phase IIa Randomized Clinical Trial - Haiqing Song; Yuan Wang; Qingfeng Ma; Huisheng Chen; Bo Liu; Yi Yang; Jianguo Zhu; Shigang Zhao; Xiaoping Jin; Yongqiu Li; Yanyong Wang; Runxiu Zhu; et al. (Translational Stroke Research, 2022)

Tectonic framework of Eastern Tianshan in the Early Carboniferous: constraints from alkalic intrusive rocks - Yi-Hao Liu; Chun-Ji Xue; Yun Zhao; Rui Wang; Liang Yu (International Journal of Earth Sciences, 2022)

Acacetin antagonized lipotoxicity in pancreatic β-cells via ameliorating oxidative stress and endoplasmic reticulum stress - Ning Wang; Qing Gao; Jie Shi; Chen Yulan; Weimeng Ji; Xiumei Sheng; Rui Zhang (Molecular Biology Reports, 2022)

Expression Quantitative Trait Locus rs6356 Is Associated with Susceptibility to Heroin Addiction by Potentially Influencing TH Gene Expression in the Hippocampus and Nucleus Accumbens - Kena Wang; Hongbo Zhang; Jinshan Ji; Rui Zhang; Wei Dang; Qiaoli Xie; Yongsheng Zhu; Jianbo Zhang (Journal of Molecular Neuroscience, 2022)

Transcriptomic Analysis of Circulating Neutrophils in Sheep with Mineral Element Imbalance - Di Wang; Ming Ji; Qijun Zhou; Chengyuan Su; Shuai Lian; Jianfa Wang; Jiasan Zheng; Rui Wu (Biological Trace Element Research, 2022)

Comparison of separated and combined photodegradation and biofiltration technology for the treatment of volatile organic compounds: A critical review - Meng-Fei Han; Xu-Rui Hu; Yong-Chao Wang; Zhen Tong; Can Wang; Zhuo-Wei Cheng; Ke Feng; Miao-Miao Qu; Jian-Meng Chen; Ji-Guang Deng; Hsing-Cheng Hsi (Critical Reviews in Environmental Science and Technology, 2022)

Alkaloids constituents from the roots of Phragmites australis (Cav.) Trin. ex Steud. with their cytotoxic activities - Ying Chen; Li Li; Li-Rui Jiang; Jia-Yin Tan; Li-Na Guo; Xiao-Li Wang; Wei Dong; Wen-Bao Wang; Ji-Kai Sun; Bo Song (Natural Product Research, 2022)

A two-phase comprehensive NSCLC prognostic study identifies lncRNAs with significant main effect and interaction - Jing Zhu; Jinxing Guan; Xinyu Ji; Yunjie Song; Xiaoshuang Xu; Qianqian Wang; Quanan Zhang; Renhua Guo; Rui Wang; Ruyang Zhang (Molecular Genetics and Genomics, 2022)
Long noncoding RNA (lncRNA) are involved in regulating physiological behaviors for various malignant tumors, including non-small-cell lung cancer (NSCLC). However, few studies comprehensively evaluated both lncRNA–lncRNA interaction effects and main effects of lncRNA on overall survival of NSCLC. Hence, we performed a two-phase designed study of lncRNA expression in tumor tissues using 604 NSCLC patients from The Cancer Genome Atlas as the discovery phase and 839 patients from Gene Expression Omnibus as the validation phase. In the discovery phase, we adopted a two-step strategy, Screening before Testing , for dimension reduction and signal detection. These candidate lncRNAs first screened out by the weighted random forest (Ranger), were then tested through the Cox proportional hazards model adjusted for covariates. Significant lncRNAs with either type of effects aforementioned were carried forward into the validation phase to confirm their significances again. As a result, in the discovery phase, 19 lncRNAs were identified by Ranger, among which five lncRNAs and one pair of lncRNA–lncRNA interaction exhibited significant effects (FDR- q ≤ 0.05) main and interaction effects on NSCLC survival, respectively, through Cox model. After the independent validation, we finally observed that one lncRNA (ENSG00000227403.1) with main effect was robustly associated with NSCLC prognosis ( HR discovery = 0.90, P = 1.20 × 10 –3 ; HR validation = 0.94, P = 4.11 × 10 –3 ) and one pair of lncRNAs (ENSG00000267121.4 and ENSG00000272369.1) had significant interaction effect on NSCLC survival ( HR discovery = 1.12, P = 3.07 × 10 –4 ; HR validation = 1.11, P = 0.0397). Our comprehensive NSCLC prognostic study of lncRNA provided population-level evidence for further functional study.

Two new threonine-containing metabolites from fungus Curvularia inaequalis strain HS-FG-257 - Shao-Yong Zhang; Jian-Song Li; Hui Zhang; Huan Qi; Rui-Jun Wang; Chou-Fei Wu; Li-Qin Zhang; An-Liang Chen; Ji-Dong Wang; Zhi-Kui Hao (Natural Product Research, 2022)

Mutual impacts and interactions of antibiotic resistance genes, microcystin synthetase genes, graphene oxide, and Microcystis aeruginosa in synthetic wastewater - Shichao Wu; Xiyan Ji; Xin Li; Jing Ye; Wenwu Xu; Rui Wang; Meifang Hou (Environmental Science and Pollution Research, 2022)

The Water Resisting Properties of the Top Portion of the Ordovician Limestone Aquifer in the North China Coalfield - Hao Wang; Shuning Dong; Rui Chai; Wei Qiao; Jian Yang; Ji Liu; Linsheng Zhou; Zhenfang Zhou; Zhaoxing Liu; Hongbo Shang (Mine Water and the Environment, 2021)

Oxiracetam Mediates Neuroprotection Through the Regulation of Microglia Under Hypoxia-Ischemia Neonatal Brain Injury in Mice - Dan Wang; Yanbang Wei; Jingxia Tian; Dong He; Rui Zhang; Xiaoshuai Ji; Xiaoming Huang; Jun Sun; Jiajia Gao; Zixiao Wang; Qi Pang; Qian Liu (Molecular Neurobiology, 2021)

Transcriptome profiling analysis of two contrasting barley genotypes in general combining ability for yield traits - Xiaodong Chen; Bin Zhao; Changhao Ji; Bin Zhu; Rui Wang (Brazilian Journal of Botany, 2021)

Astrocyte-Derived Lactate Modulates the Passive Coping Response to Behavioral Challenge in Male Mice - Ya-Nan Yin; Jian Hu; Yi-Li Wei; Ze-Lin Li; Zhou-Cai Luo; Rui-Qi Wang; Ke-Xin Yang; Shu-Ji Li; Xiao-Wen Li; Jian-Ming Yang; Tian-Ming Gao (Neuroscience Bulletin, 2021)

Hydrogeochemical and isotopic characteristics of groundwater in Xinchang preselected site and their implications - Zhichao Zhou; Ju Wang; Rui Su; Yonghai Guo; Jingbo Zhao; Ming Zhang; Ruili Ji; Yanan Li; Jiebiao Li (Environmental Science and Pollution Research, 2020)

Prefrontal Nectin3 Reduction Mediates Adolescent Stress-Induced Deficits of Social Memory, Spatial Working Memory, and Dendritic Structure in Mice - Hong-Li Wang; Ji-Tao Li; Han Wang; Ya-Xin Sun; Rui Liu; Xiao-Dong Wang; Yun-Ai Su; Tian-Mei Si (Neuroscience Bulletin, 2020)
Chronic stress may disrupt the normal neurodevelopmental trajectory of the adolescent brain (especially the prefrontal cortex) and contribute to the pathophysiology of stress-related mental illnesses, but the underlying molecular mechanisms remain unclear. Here, we investigated how synaptic cell adhesion molecules (e.g., nectin3) are involved in the effects of adolescent chronic stress on mouse medial prefrontal cortex (mPFC). Male C57BL/6N mice were subjected to chronic social instability stress from postnatal days 29 to 77. One week later, the mice exposed to chronic stress exhibited impaired social recognition and spatial working memory, simplified dendritic structure, and reduced spine density in the mPFC. Membrane localization of nectin3 was also altered, and was significantly correlated with behavioral performance. Furthermore, knocking down mPFC nectin3 expression by adeno-associated virus in adolescent mice reproduced the stress-induced changes in behavior and mPFC morphology. These results support the hypothesis that nectin3 is a potential mediator of the effects of adolescent chronic stress on prefrontal structural and functional abnormalities.

Mapping and characterization of major QTL for spike traits in common wheat - Cheng-Hao Kuang; Xiao-Fang Zhao; Ke Yang; Zhi-Peng Zhang; Li Ding; Zhi-En Pu; Jian Ma; Qian-Tao Jiang; Guo-Yue Chen; Ji-Rui Wang; Yu-Ming Wei; You-Liang Zheng; et al. (Physiology and Molecular Biology of Plants, 2020)

Antifungal Activity of Magnesium Oxide Nanoparticles: Effect on the Growth and Key Virulence Factors of Candida albicans - Fanzhi Kong; Jiaying Wang; Rui Han; Shuaiqi Ji; Jin Yue; Yongliang Wang; Lei Ma (Mycopathologia, 2020)

Tracing solute sources and carbon dynamics under various hydrological conditions in a karst river in southwestern China - Jing Liu; Bo Chen; Zhu-Yan Xu; Yuan Wei; Zhi-Hua Su; Rui Yang; Yong-Xue Ji; Xiao-Dan Wang; Li-Li Zhang; Ning An; Fei Yang (Environmental Science and Pollution Research, 2020)

Impact of Arctic amplification on declining spring dust events in East Asia - Jun Liu; Dongyou Wu; Guangjing Liu; Rui Mao; Siyu Chen; Mingxia Ji; Pingqing Fu; Yele Sun; Xiaole Pan; Hongchun Jin; Yubin Zhou; Xin Wang (Climate Dynamics, 2020)
Dust aerosols play key roles in affecting regional and global climate through their direct, indirect, and semi-direct effects. Dust events have decreased rapidly since the 1980s in East Asia, particularly over northern China, primarily because of changes in meteorological parameters (e.g. surface wind speed and precipitation). In this study, we found that winter (December–January–February) Arctic amplification associated with weakened temperature gradients along with decreased zonal winds is primarily responsible for the large decline in following spring (March–April–May) dust event occurrences over northern China since the mid-1980s. A dust index was developed for northern China by combining the daily frequency of three types of dust event (dust storm, blowing dust, and floating dust). Using the empirical orthogonal function (EOF) analysis, the first pattern of dust events was obtained for spring dust index anomalies, which accounts for 56.2% of the variability during 1961–2014. Moreover, the enhanced Arctic amplification and stronger Northern Hemisphere annular mode (NAM) in winter can result in the anticyclonic anomalies over Siberia and Mongolia, while cyclonic anomalies over East Europe in spring. These results are significantly correlated with the weakened temperature gradients, increased precipitation and soil moisture, and decreased snow cover extent in the mid-latitude over Northern Hemisphere. Based on the future predictions obtained from the Fifth Climate Models Intercomparison Project (CMIP5), we found that the dust event occurrences may continually decrease over northern China due to the enhanced Arctic amplification in future climate.

Wind and sand control by an oasis protective system: a case from the southeastern edge of the Tengger Desert, China - Yun-hu Xie; Xiao-hong Dang; Zhong-ju Meng; Hong-tao Jiang; Xiao-jia Li; Rui-ping Zhou; Dan-dan Zhou; Xiao-xi Liu; Jing Ding; Xue-qin Wu; Yu-hao Wang; Chun-xing Hai; et al. (Journal of Mountain Science, 2019)

Responses of nitrification and denitrification to nitrogen and phosphorus fertilization: does the intrinsic soil fertility matter? - Ying Wang; Hongfei Ji; Rui Wang; Shengli Guo (Plant and Soil, 2019)

Effects of different substrates on nitrogen and phosphorus removal in horizontal subsurface flow constructed wetlands - Rui Xu; Yong Zhang; Rong Liu; Yun Cao; Guoxiang Wang; Lingchen Ji; Yifan Xu (Environmental Science and Pollution Research, 2019)

Synthesis and biological evaluation of disulfides bearing 1,2,4-triazole moiety as antiproliferative agents - Xue-Feng Wang; Shuai Zhang; Bao-Lin Li; Ji-Jun Zhao; Yu-Ming Liu; Rui-Lian Zhang; Bo Li; Bao-Quan Chen (Medicinal Chemistry Research, 2017)

Nominal effective immunoreaction volume of magnetic beads at single bead level - Rui Wang; Yuan Chen; Kai Fan; Feng Ji; Jian Wu; Yong-hua Yu (Journal of Zhejiang University-SCIENCE B, 2017)

Allometric equations of select tree species of the Tibetan Plateau, China - Fei Ran; Rui-ying Chang; Yang Yang; Wan-ze Zhu; Ji Luo; Gen-xu Wang (Journal of Mountain Science, 2017)

Erratum to: Transposon insertion resulted in the silencing of Wx-B1n in Chinese wheat landraces - Ling‑Ling Zhang; Hu Chen; Mi Luo; Xiao‑Wei Zhang; Mei Deng; Jian Ma; Peng‑Fei Qi; Ji‑Rui Wang; Guo‑Yue Chen; Ya‑Xi Liu; Zhi‑En Pu; Wei Li; et al. (Theoretical and Applied Genetics, 2017)

Transposon insertion resulted in the silencing of Wx-B1n in Chinese wheat landraces - Ling-Ling Zhang; Hu Chen; Mi Luo; Xiao-Wei Zhang; Mei Deng; Jian Ma; Peng-Fei Qi; Ji-Rui Wang; Guo-Yue Chen; Ya-Xi Liu; Zhi-En Pu; Wei Li; et al. (Theoretical and Applied Genetics, 2017)

The Research on the Relationship of RAGE, LRP-1, and Aβ Accumulation in the Hippocampus, Prefrontal Lobe, and Amygdala of STZ-Induced Diabetic Rats - Lou-Yan Ma; Yu-Lang Fei; Xiao-Ye Wang; Song-Di Wu; Jun-Hui Du; Mei Zhu; Long Jin; Ming Li; Hai-Long Li; Jia-Jia Zhai; Lu-Peng Ji; Ran-Ran Ma; et al. (Journal of Molecular Neuroscience, 2017)

Warming Effects on Ecosystem Carbon Fluxes Are Modulated by Plant Functional Types - Ji Chen; Yiqi Luo; Jianyang Xia; Kevin R. Wilcox; Junji Cao; Xuhui Zhou; Lifen Jiang; Shuli Niu; Katerina Y. Estera; Rujin Huang; Feng Wu; Tafeng Hu; et al. (Ecosystems, 2017)

Costimulation of soil glycosidase activity and soil respiration by nitrogen addition - Ji Chen; Yiqi Luo; Jianwei Li; Xuhui Zhou; Junji Cao; Rui‐Wu Wang; Yunqiang Wang; Shelby Shelton; Zhao Jin; Laura M. Walker; Zhaozhong Feng; Shuli Niu; et al. (Global Change Biology, 2017)
Unprecedented levels of nitrogen (N) have been deposited in ecosystems over the past century, which is expected to have cascading effects on microbially mediated soil respiration ( SR ). Extracellular enzymes play critical roles on the degradation of soil organic matter, and measurements of their activities are potentially useful indicators of SR . The links between soil extracellular enzymatic activities ( EEA s) and SR under N addition, however, have not been established. We therefore conducted a meta‐analysis from 62 publications to synthesize the responses of soil EEA s and SR to elevated N. Nitrogen addition significantly increased glycosidase activity ( GA ) by 13.0%, α ‐1,4‐glucosidase ( AG ) by 19.6%, β ‐1,4‐glucosidase ( BG ) by 11.1%, β ‐1,4‐xylosidase ( BX ) by 21.9% and β ‐D‐cellobiosidase ( CBH ) by 12.6%. Increases in GA were more evident for long duration, high rate, organic and mixed N addition (combination of organic and inorganic N addition), as well as for studies from farmland. The response ratios ( RR s) of GA were positively correlated with the SR ‐ RR s, even when evaluated individually for AG , BG , BX and CBH . This positive correlation between GA ‐ RR and SR ‐ RR was maintained for most types of vegetation and soil as well as for different methods of N addition. Our results provide the first evidence that GA is linked to SR under N addition over a range of ecosystems and highlight the need for further studies on the response of other soil EEA s to various global change factors and their implications for ecosystem functions.

Sequence analysis and expression profiles of TaABI5, a pre-harvest sprouting resistance gene in wheat - Ke Zhou; Jian Yang; Zao-Xia Wang; Ji-Rui Wang (Genes & Genomics, 2017)

Nurr1 promotes intestinal regeneration after ischemia/reperfusion injury by inhibiting the expression of p21 (Waf1/Cip1) - Guo Zu; Jihong Yao; Anlong Ji; Shili Ning; Fuwen Luo; Zhenlu Li; Dongcheng Feng; Yiqi Rui; Yang Li; Guangzhi Wang; Xiaofeng Tian (Journal of Molecular Medicine, 2017)

Molecular cloning and characterization of α-amylase/subtilisin inhibitor from rhizome of Ligusticum chuanxiong - Ji-hua Yu; Yang-yang Li; Mian Xiang; Jian-quan Zhu; Xin-he Huang; Wan-Jun Wang; Rui Tan; Jia-yu Zhou; Hai Liao (Biotechnology Letters, 2017)

Early postnatal stress suppresses the developmental trajectory of hippocampal pyramidal neurons: the role of CRHR1 - Rui Liu; Xiao-Dun Yang; Xue-Mei Liao; Xiao-Meng Xie; Yun-Ai Su; Ji-Tao Li; Xiao-Dong Wang; Tian-Mei Si (Brain Structure and Function, 2016)

Sonic Hedgehog Signaling Affected by Promoter Hypermethylation Induces Aberrant Gli2 Expression in Spina Bifida - Xiao-Lin Lu; Li Wang; Shao-Yan Chang; Shao-Fang Shangguan; Zhen Wang; Li-Hua Wu; Ji-Zhen Zou; Ping Xiao; Rui Li; Yi-Hua Bao; Z-Y Qiu; Ting Zhang (Molecular Neurobiology, 2016)

Tissue Transglutaminase and Its Product Isopeptide Are Increased in Alzheimer’s Disease and APPswe/PS1dE9 Double Transgenic Mice Brains - Ji Zhang; Suqing Wang; Wei Huang; David A. Bennett; Dennis W. Dickson; Dengshun Wang; Rui Wang (Molecular Neurobiology, 2016)

Characterization and expression analyses of the H+-pyrophosphatase gene in rye - CHANG-SHUI WANG; QIAN-TAO JIANG; JIAN MA; XIU-YING WANG; JI-RUI WANG; GUO-YUE CHEN; PENG-FEI QI; YUAN-YING PENG; XIU-JIN LAN; YOU-LIANG ZHENG; YU-MING WEI (Journal of Genetics, 2016)

Characterization of the waxy gene in diploid Triticum L. and Aegilops L. species and its geographic distribution - Wei Li; Bang-Bo Fu; Zhe Li; Ya-Xi Liu; Zhi-En Pu; Peng-Fei Qi; Qian-Tao Jiang; Guo-Yue Chen; Ji-Rui Wang; Yu-Ming Wei; You-Liang Zheng (Genetic Resources and Crop Evolution, 2016)

Structure and expression of phosphoglucan phosphatase genes of Like Sex Four1 and Like Sex Four2 in barley - Jian Ma; Shang Gao; Qian-Tao Jiang; Qiang Yang; Min Sun; Ji-Rui Wang; Peng-Fei Qi; Ya-Xi Liu; Wei Li; Zhi-En Pu; Xiu-Jin Lan; Yu-Ming Wei; et al. (Genetica, 2016)

Identification of a Novel Rat NR2B Subunit Gene Promoter Region Variant and Its Association with Microwave-Induced Neuron Impairment - Li-Feng Wang; Da-Wei Tian; Hai-Juan Li; Ya-Bing Gao; Chang-Zhen Wang; Li Zhao; Hong-Yan Zuo; Ji Dong; Si-Mo Qiao; Yong Zou; Lu Xiong; Hong-Mei Zhou; et al. (Molecular Neurobiology, 2016)

Oral administration of Anabaena-expressed VP28 for both drug and food against white spot syndrome virus in shrimp - Xiao-Hui Jia; Chun-Li Zhang; Ding-Ji Shi; Min-Min Zhuang; Xiang Wang; Rui Jia; Zheng-Yang Zhang; Jie Huang; Yi-Hua Sun; Wen-Yi Qian; Guo-Hong Peng; Pei-Min He (Journal of Applied Phycology, 2016)

Effect of abiotic stress on the gameophyte of Pyropia katadae var. hemiphylla (Bangiales, Rhodophyta) - Wen-Jun Wang; Xiu-Tao Sun; Fu-Li Liu; Zhou-Rui Liang; Ji-Hong Zhang; Fei-Jiu Wang (Journal of Applied Phycology, 2016)

Molecular identification and expression of the Foxl2 gene during gonadal sex differentiation in northern snakehead Channa argus - Dan-Dan Wang; Gui-Rong Zhang; Kai-Jian Wei; Wei Ji; Jonathan P. A. Gardner; Rui-Bin Yang; Kun-Ci Chen (Fish Physiology and Biochemistry, 2015)

Transcriptome profiling reveals auxin suppressed anthocyanin biosynthesis in red-fleshed apple callus (Malus sieversii f. niedzwetzkyana) - Xiao-Hao Ji; Rui Zhang; Nan Wang; Long Yang; Xue-Sen Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Molecular cloning and characterization of caffeic acid 3-O-methyltransferase from the rhizome of Ligusticum chuanxiong - Juan-Juan Li; Gan Zhang; Ji-hua Yu; Yang-yang Li; Xin-he Huang; Wan-Jun Wang; Rui Tan; Jia-yu Zhou; Hai Liao (Biotechnology Letters, 2015)

Effect of irrigation on the soil respiration of constructed grasslands in Inner Mongolia, China - Ji–Rui Gong; Sha Xu; Yihui Wang; Qinpu Luo; Min Liu; Wei Zhang (Plant and Soil, 2015)

Characterization of genes encoding Starch Branching Enzyme I from Triticum monococcum and its diploid wheat relatives - Xiu-Ying Wang; Chang-Shui Wang; Jian Ma; Ji-Rui Wang; Ya-Xi Liu; Peng-Fei Qi; Wei Li; Zhi-En Pu; Xiu-Jin Lan; Yu-Ming Wei; You-Liang Zheng; Qian-Tao Jiang (Biologia, 2015)

Activation of VEGF/Flk-1-ERK Pathway Induced Blood–Brain Barrier Injury After Microwave Exposure - Li-Feng Wang; Xiang Li; Ya-Bing Gao; Shui-Ming Wang; Li Zhao; Ji Dong; Bin-Wei Yao; Xin-Ping Xu; Gong-Min Chang; Hong-Mei Zhou; Xiang-Jun Hu; Rui-Yun Peng (Molecular Neurobiology, 2015)

(Z)-3-Hexenal, One of the Green Leaf Volatiles, Increases Susceptibility of Rice to the White-Backed Planthopper Sogatella furcifera - Baohui Wang; Guoxin Zhou; Zhaojun Xin; Rui Ji; Yonggen Lou (Plant Molecular Biology Reporter, 2015)

Quantitative trait locus mapping for seed dormancy in different post-ripening stages in a Tibetan semi-wild wheat (Triticum aestivum ssp. tibetanum Shao) - Yun-Feng Jiang; Ji-Rui Wang; Wei Luo; Yu-Ming Wei; Peng-Fei Qi; Ya-Xi Liu; Qian-Tao Jiang; Yuan-Ying Peng; Guo-Yue Chen; Shou-Fen Dai; You-Liang Zheng; Xiu-Jin Lan (Euphytica, 2015)

Anxiolytic effects of ketamine in animal models of posttraumatic stress disorder - Li-Ming Zhang; Wen-Wen Zhou; Ya-Jun Ji; Ying Li; Nan Zhao; Hong-Xia Chen; Rui Xue; Xin-Guo Mei; You-Zhi Zhang; Heng-Lin Wang; Yun-Feng Li (Psychopharmacology, 2015)

Effect of auxin, cytokinin and nitrogen on anthocyanin biosynthesis in callus cultures of red-fleshed apple (Malus sieversii f.niedzwetzkyana) - Xiao-Hao Ji; Yan-Ting Wang; Rui Zhang; Shu-Jing Wu; Meng-Meng An; Min Li; Chuan-Zeng Wang; Xiao-Liu Chen; Yan-Min Zhang; Xue-Sen Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Upregulation of HIF-1α Via Activation of ERK and PI3K Pathway Mediated Protective Response to Microwave-Induced Mitochondrial Injury in Neuron-Like Cells - Li Zhao; Yue-Feng Yang; Ya-Bing Gao; Shui-Ming Wang; Li-Feng Wang; Hong-Yan Zuo; Ji Dong; Xin-Ping Xu; Zhen-Tao Su; Hong-Mei Zhou; Ling-Ling Zhu; Rui-Yun Peng (Molecular Neurobiology, 2014)

Toxic effects of sodium fluoride on cell proliferation and apoptosis of Leydig cells from young mice - Guo hua Song; Rui Li Wang; Zhao Yang Chen; Bin Zhang; Hai Long Wang; Mao Lin Liu; Ji Ping Gao; Xiao Yan Yan (Journal of Physiology and Biochemistry, 2014)

Molecular cloning and expression analysis of mannose receptor in blunt snout bream (Megalobrama amblycephala) - Xiaoling Liu; Xiaocheng Tang; Li Wang; Jie Li; Hong Wang; Shun Wei; Rui Fang; Wei Ji; Gailing Yuan; Nan Chen; Zemao Gu; Xueqin Liu; et al. (Molecular Biology Reports, 2014)

Isolation and characterization of twenty-three polymorphic microsatellite loci in Schizothorax macropogon - Xiang-Zhao Guo; Gui-Rong Zhang; Ruo-Jin Yan; Wei Ji; Rui-Bin Yang; Kai-Jian Wei; Deng-Qiang Wang (Conservation Genetics Resources, 2014)

Wheat gene TaS3 contributes to powdery mildew susceptibility - Shaohui Li; Rui Ji; Robert Dudler; Mingli Yong; Qide Deng; Zhengyi Wang; Dongwei Hu (Plant Cell Reports, 2013)

In vitro mutagenesis and directed screening for salt-tolerant mutants in peanut - Ming-Xia Zhao; Hai-Yan Sun; Rui-Rui Ji; Xiao-Hui Hu; Jiong-Ming Sui; Li-Xian Qiao; Jing Chen; Jing-Shan Wang (Euphytica, 2013)

Litorilituus sediminis gen. nov. sp. nov., isolated from coastal sediment of an amphioxus breeding zone in Qingdao, China - Yan Wang; Rui Zhao; Shiqi Ji; Zhao Li; Tong Yu; Bingyu Li; Xiaochong Shi; Xiao-Hua Zhang (Antonie van Leeuwenhoek, 2013)

A novel Trichoderma species isolated from soil in Guizhou, T. guizhouense - Qi-Rui Li; Ping Tan; Yu-Lan Jiang; Kevin D. Hyde; Eric H. C. Mckenzie; Ali H. Bahkali; Ji-Chuan Kang; Yong Wang (Mycological Progress, 2013)

Identification of 40k γ-secalin genes - PENG-FEI QI; QING CHEN; THÉRÈSE OUELLET; CHENG-XING LE; JIA AI; YU-MING WEI; JI-RUI WANG; YOU-LIANG ZHENG (Journal of Genetics, 2013)

Litoribacillus peritrichatus gen. nov. sp. nov., isolated from coastal sediment of an amphioxus breeding zone in Qingdao, China - Rui Zhao; Shiqi Ji; Yan Wang; Tong Yu; Zhao Li; Bingyu Li; Xiaochong Shi; Xiao-Hua Zhang (Antonie van Leeuwenhoek, 2013)

Meta-analysis of QTL associated with tolerance to abiotic stresses in barley - Wei-Tao Li; Chunji Liu; Ya-Xi Liu; Zhi-En Pu; Shou-Fen Dai; Ji-Rui Wang; Xiu-Jin Lan; You-Liang Zheng; Yu-Ming Wei (Euphytica, 2013)

Haplotype variations of gene Ppd-D1 in Aegilops tauschii and their implications on wheat origin - Lin Huang; Qing Wang; Lian-Quan Zhang; Zhong-Wei Yuan; Ji-Rui Wang; Huai-Gang Zhang; You-Liang Zheng; Deng-Cai Liu (Genetic Resources and Crop Evolution, 2012)

Novel HMW glutenin genes from Aegilops tauschii and their unique structures - Wen-Jie Chen; Zhong-Wei Yuan; Lian-Quan Zhang; Xing Fan; Ze-Hong Yan; Ji-Rui Wang; You-Liang Zheng; Huai-Gang Zhang; Deng-Cai Liu (Genes & Genomics, 2012)

siRNAs target sites selection of ezrin and the influence of RNA interference on ezrin expression and biological characters of osteosarcoma cells - XiFu Shang; YaoFei Wang; QiChun Zhao; KeRong Wu; Xu Li; XiaoFeng Ji; Rui He; WenZhi Zhang (Molecular and Cellular Biochemistry, 2012)

Echinococcus granulosus: Immunoprotection accompanyied by humoral and cytokine response against secondary hydatidosis in mice immunized with rEg.myophilin - Junfeng Sun; Yana Wang; Zongji Li; Rui Ma; Haiqing Ji; Ying Xiong; Yin Wang; Zhaoyu Li; Wei Zhao (Veterinary Research Communications, 2011)

Nicotinic acetylcholine receptor alpha7 subunit is time-dependently expressed in distinct cell types during skin wound healing in mice - Yan-Yan Fan; Tian-Shui Yu; Tao Wang; Wei-Wei Liu; Rui Zhao; Shu-Tao Zhang; Wen-Xiang Ma; Ji-Long Zheng; Da-Wei Guan (Histochemistry and Cell Biology, 2011)

Multiple induced mutagenesis for improvement of ethanol production by Kluyveromyces marxianus - Zong-wen Pang; Jing-juan Liang; Xiao-juan Qin; Ji-rui Wang; Jia-xun Feng; Ri-bo Huang (Biotechnology Letters, 2010)

Genome-wide identification and evaluation of novel internal control genes for Q-PCR based transcript normalization in wheat - Xiang-Yu Long; Ji-Rui Wang; Thérèse Ouellet; Hélène Rocheleau; Yu-Ming Wei; Zhi-En Pu; Qian-Tao Jiang; Xiu-Jing Lan; You-Liang Zheng (Plant Molecular Biology, 2010)

Identification, localization, and characterization of putative USP genes in barley - Wei-Tao Li; Yu-Ming Wei; Ji-Rui Wang; Chun-Ji Liu; Xiu-Jin Lan; Qian-Tao Jiang; Zhi-En Pu; You-Liang Zheng (Theoretical and Applied Genetics, 2010)

Molecular diversity and phylogenetic analyses of y-type high-molecular-weight glutenin promoters from different genomes in Triticeae - Qian-Tao Jiang; Yu-Ming Wei; Ji-Rui Wang; Ze-Hong Yan; You-Liang Zheng (Plant Systematics and Evolution, 2010)

SSR and SCAR mapping of a multiple-allele male-sterile gene in Chinese cabbage (Brassica rapa L.) - Hui Feng; Peng Wei; Zhong-Yun Piao; Zhi-Yong Liu; Cheng-Yu Li; Yu-Gang Wang; Rui-Qin Ji; Shu-Juan Ji; Ting Zou; Su-Ryun Choi; Yong-Pyo Lim (Theoretical and Applied Genetics, 2009)

Molecular Characterization of the pina Gene in Einkorn Wheat - Qing Chen; Peng-Fei Qi; Yu-Ming Wei; Ji-Rui Wang; You-Liang Zheng (Biochemical Genetics, 2009)

Mechanisms underlying low [Ca2+]o-induced increased excitability of hippocampal neurons - Wei-Dong Yue; Yun-Hong Zhang; Feng Gu; Jing Wang; Ji-Ye Zhang; Rui-Min Gu (Neuroscience Bulletin, 2008)

SNP and haplotype identification of the wheat monomeric α-amylase inhibitor genes - Ji-Rui Wang; Yu-Ming Wei; Ze-Hong Yan; You-Liang Zheng (Genetica, 2008)

Sequence Variations and Haplotype Identification of Wheat Dimeric α-Amylase Inhibitor Genes in Einkorn Wheats - Ji-Rui Wang; Yu-Ming Wei; Ze-Hong Yan; You-Liang Zheng (Biochemical Genetics, 2007)

Genetic mapping of the wheat dimeric α-amylase inhibitor multi-gene family using allele-specific primers based on intergenomic SNPs - Ji-Rui Wang; Yu-Ming Wei; Ze-Hong Yan; You-Liang Zheng (Plant Molecular Biology Reporter, 2006)

Characterization of two HMW glutenin subunit genes from Taenitherum Nevski - Ze-Hong Yan; Yu-Ming Wei; Ji-Rui Wang; Deng-Cai Liu; Shou-Fen Dai; You-Liang Zheng (Genetica, 2006)

A high-molecular-weight glutenin subunit gene 1Dx2.1 from Xinjiang rice wheat - Qian-Tao Jiang; Yu-Ming Wei; Ji-Rui Wang; Ze-Hong Yan; You-Liang Zheng (Cereal Research Communications, 2005)

Safety analysis of water resources and eco-environment in Shiyang River Basin - Ji-shi Zhang; Yong-qiu Zhang; Rui-feng Pu; Ren-sheng Chen; Zhong-shan Cheng; Ming-quan Wang (Chinese Geographical Science, 2005)

New progress of research on water cycle in atmosphere in China - Wang Guo; Jia Shao-feng; Yu Gui-rui; Xu Juan; Wang Jin-xia; Wang Qiu-feng; Ge Quan-sheng; Huang Ji-kun; Xia Jun; Li Li-fnjuan; Jin De-sheng; Dong Suo-cheng; et al. (Journal of Geographical Sciences, 2001)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)